Exterior material for electricity storage device, method for producing same, and electricity storage device
By using a laminated structure of a base layer, a barrier layer and a hot-weld resin layer in the exterior materials for power storage devices, the logarithmic attenuation rate of the hot-weld resin layer is controlled, and the problem of degradation of insulation at high temperatures is solved, and the problem of reducing insulation at high temperatures is improved. Sealing and stability.
Patent Information
- Application Number
- CN202411333471.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2018-10-24
- Filing Date
- 2019-10-24
- Publication Date
- 2024-12-31
AI Technical Summary
In the high temperature and high pressure conditions of the existing external materials for electric storage devices, the insulation of the hot-welded resin layer is easily reduced, resulting in damage to the sealing properties of the components.
The laminated body structure consisting of a base material layer, a barrier layer and a hot-weld resin layer, wherein the logarithmic attenuation rate ΔE of the first layer of the hot-weld resin layer is 0.20 or less at 140°C. The resin layer is adjusted by adjusting the The structure and structure are used to suppress destruction of the thermally welded resin layer.
It effectively improves the high temperature resistance of the hot-welded resin layer, prevents the insulating property from decreasing, and enhances the sealing and stability of the power storage device.
Smart Images

Figure CN119231041A_ABST
Abstract
Description
[0001] (This application is a divisional application of application No. 201980070567.7, filed on October 24, 2019, entitled “Exterior material for power storage device, method for manufacturing the same, and power storage device”) Technical Field
[0002] The present invention relates to an exterior material for an electricity storage device, a method for producing the exterior material, and an electricity storage device. Background Art
[0003] In the prior art, various types of power storage devices have been developed, and in all power storage devices, packaging materials have become an indispensable component in order to encapsulate power storage device elements such as electrodes and electrolytes. In the prior art, metal packaging materials are often used as external packaging materials for power storage devices.
[0004] On the other hand, in recent years, with the high performance of electric vehicles, hybrid electric vehicles, computers, cameras, mobile phones, etc., storage devices need to have various shapes, and also need to be thinner and lighter. However, the metal exterior materials for storage devices currently used are difficult to cope with the diversity of shapes and have a limit to lightweight.
[0005] Therefore, in recent years, as an exterior material for a storage battery device that can be easily processed into various shapes and can achieve thinning and lightening, a film-like laminated body in which a base layer / barrier layer / thermofusible resin layer are laminated in sequence has been proposed (see, for example, Patent Document 1).
[0006] In such an external packaging material for a storage device, a recess is usually formed by cold forming, storage device elements such as electrodes and electrolyte are arranged in the space formed by the recess, and a heat-fusible resin layer is heat-fused to obtain a storage device in which the storage device elements are accommodated inside the external packaging material for the storage device.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2008-287971 Summary of the invention
[0010] Technical problem to be solved by the invention
[0011] When sealing the storage device element, a high temperature and a high pressure are applied to the storage device packaging material using a metal plate, etc., so that the heat-fusible resin layer is heat-fused. However, the inventors of the present invention have found that applying a high temperature and a high pressure to the storage device packaging material may cause the heat-fusible resin layer on the surface to collapse, resulting in a decrease in the insulation of the storage device packaging material.
[0012] Under such circumstances, the main object of the present invention is to provide an external packaging material for a power storage device composed of a laminate having at least a base layer, a barrier layer and a heat-fusible resin layer in this order, which can effectively prevent the heat-fusible resin layer from being destroyed during heat fusion.
[0013] Technical means for solving technical problems
[0014] In order to solve the above-mentioned technical problems, the inventors of the present invention have conducted in-depth research and found that: an external packaging material for a storage device, which is composed of a laminate having at least a base layer, a barrier layer and a heat-fusible resin layer in sequence, the heat-fusible resin layer being composed of a single layer or a plurality of layers, and the first heat-fusible resin layer constituting the surface of the laminate in the heat-fusible resin layer having a logarithmic attenuation rate ΔE of less than 0.20 at 140°C in a rigid body oscillator measurement, can effectively suppress the destruction of the heat-fusible resin layer during heat welding.
[0015] The present invention has been completed by further repeated studies based on these findings. That is, the present invention provides the following aspects.
[0016] A packaging material for a storage device, comprising a laminate having at least a substrate layer, a barrier layer and a heat-fusible resin layer in sequence, wherein the heat-fusible resin layer is composed of a single layer or a plurality of layers, and among the heat-fusible resin layers, the first heat-fusible resin layer constituting the surface of the laminate has a logarithmic attenuation rate ΔE of less than 0.20 at 140°C in a rigid body oscillator measurement.
[0017] Effects of the Invention
[0018] According to the present invention, it is possible to provide an external packaging material for a storage device, which is composed of a laminated body having at least a base layer, a barrier layer, and a heat-fusible resin layer in this order, and can effectively suppress the heat-fusible resin layer from being destroyed during heat fusion. By suppressing the destruction, it is possible to expect, for example, improvement in insulation. In addition, according to the present invention, it is also possible to provide a method for manufacturing an external packaging material for a storage device and a storage device. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic diagram showing an example of the cross-sectional structure of the external packaging material for an electric storage device of the present invention.
[0020] Figure 2 It is a schematic diagram showing an example of the cross-sectional structure of the external packaging material for an electric storage device of the present invention.
[0021] Figure 3 It is a schematic diagram showing an example of the cross-sectional structure of the external packaging material for an electric storage device of the present invention.
[0022] Figure 4It is a schematic diagram showing an example of the cross-sectional structure of the external packaging material for an electric storage device of the present invention.
[0023] Figure 5 It is a schematic diagram showing an example of the cross-sectional structure of the external packaging material for an electric storage device of the present invention.
[0024] Figure 6 This is a schematic diagram for explaining a method for measuring the logarithmic decrement ΔE using a rigid body oscillator measurement.
[0025] Figure 7 This is a microscopic photograph of a cross section of a thermally welded portion between thermally welded resin layers of the power storage device exterior material obtained in Example 1 (taken at a magnification of 20 times).
[0026] Figure 8 This is a microscopic photograph of a cross section of a thermally welded portion between thermally welded resin layers of the electricity storage device exterior material obtained in Example 2 (photographed at a magnification of 20 times).
[0027] Fig. 9 This is a microscopic photograph of a cross section of a thermally welded portion between thermally welded resin layers of the power storage device exterior material obtained in Comparative Example 1 (taken at a magnification of 20 times).
[0028] Fig.10 This is a microscopic photograph of a cross section of a thermally welded portion between thermally welded resin layers of the power storage device exterior material obtained in Comparative Example 2 (taken at a magnification of 20 times).
[0029] Fig.11 It is a schematic diagram for explaining the protrusion formed inside the heat-welding portion of the heat-welding resin layer. DETAILED DESCRIPTION
[0030] The external packaging material for a power storage device of the present invention is characterized in that it is composed of a laminate having at least a base layer, a barrier layer, and a heat-fusible resin layer in this order, the heat-fusible resin layer is composed of a single layer or a plurality of layers, and the first heat-fusible resin layer constituting the surface of the laminate has a logarithmic decrement ΔE of 0.20 or less at 140° C. in a rigid body oscillator measurement. According to the external packaging material for a power storage device of the present invention, by having this feature, it is possible to effectively suppress the heat-fusible resin layer from being destroyed during heat fusion.
[0031] Hereinafter, the external packaging material for an electric storage device of the present invention will be described in detail. In this specification, the numerical range indicated by "to" means "above" or "below". For example, the expression of 2 to 15 mm means above 2 mm and below 15 mm.
[0032] 1. Laminated structure of exterior materials for power storage devices
[0033] For example, Figure 1 to Figure 5 As shown, the external packaging material 10 for a storage device of the present invention is composed of a laminate having at least a base layer 1, a barrier layer 3, and a heat-fusible resin layer 4 in this order. In the external packaging material 10 for a storage device, the base layer 1 is the outermost layer, and the heat-fusible resin layer 4 is the innermost layer. In the external packaging material 10 for a storage device of the present invention, the heat-fusible resin layer 4 is composed of a single layer or a plurality of layers, and among the heat-fusible resin layers 4, the first heat-fusible resin layer 41 constitutes the surface of the laminate. Figure 1 and Figure 2 4 shows that the heat-fusible resin layer 4 is composed of a single layer of the first heat-fusible resin layer 41, and the first heat-fusible resin layer 41 constitutes the laminated structure on the surface of the laminated body. Figure 3 to Figure 5 4 shows that the heat-fusible resin layer 4 is composed of a plurality of layers (two layers) of a first heat-fusible resin layer 41 and a second heat-fusible resin layer 42, and the first heat-fusible resin layer 41 constitutes a laminated structure on the surface of the laminate. In addition, as described later, the heat-fusible resin layer 4 may have other heat-fusible resin layers such as a third heat-fusible resin layer and a fourth heat-fusible resin layer on the barrier layer 3 side of the second heat-fusible resin layer 42 in addition to the first heat-fusible resin layer 41 and the second heat-fusible resin layer 42.
[0034] When assembling an electric storage device using the electric storage device packaging material 10 and the electric storage device element, the first heat-fusible resin layers 41 of the electric storage device packaging material 10 are placed facing each other and their peripheral edges are heat-fused to accommodate the electric storage device element in the space formed thereby.
[0035] The external packaging material 10 for a power storage device may be, for example, Figure 2 to Figure 5 As shown, between the base layer 1 and the barrier layer 3, there is an adhesive layer 2 as needed for the purpose of improving the adhesion between these layers. Figure 2 , Figure 4 and Figure 5 As shown in FIG. 1 , an adhesive layer 5 is provided between the barrier layer 3 and the heat-fusible resin layer 4 as required for the purpose of improving the adhesion between these layers. Figure 5 As shown, a surface coating layer 6 or the like may be provided on the outer side of the base material layer 1 (the side opposite to the thermally fusible resin layer 4 side) as required.
[0036] There is no particular limitation on the thickness of the laminate constituting the external packaging material 10 for a storage device. However, from the viewpoints of reducing costs and improving energy density, it is preferably about 180 μm or less and about 155 μm or less. From the viewpoint of maintaining the function of the external packaging material for a storage device to protect the storage device elements, it is preferably about 35 μm or more, about 45 μm or more, about 60 μm or more. As for the preferred range, for example, about 35 to 180 μm, about 35 to 155 μm, about 45 to 180 μm, about 45 to 155 μm, about 60 to 180 μm, and about 60 to 155 μm can be listed.
[0037] 2. Forming each layer of the exterior material for the power storage device
[0038] [Base material layer 1]
[0039] In the present invention, the base material layer 1 is a layer provided for the purpose of fulfilling the function as a base material of the external packaging material for a power storage device, etc. The base material layer 1 is located on the outer layer side of the external packaging material for a power storage device.
[0040] There are no particular limitations on the material for forming the base layer 1 as long as it can function as a base material, that is, has at least insulating properties. The base layer 1 can be formed using, for example, a resin, and the resin may contain additives described below.
[0041] When the substrate layer 1 is formed by a resin, the substrate layer 1 may be, for example, a resin film formed by a resin, or a substrate formed by coating a resin. The resin film may be an unstretched film or a stretched film. As a stretched film, a uniaxially stretched film and a biaxially stretched film may be cited, preferably a biaxially stretched film. As a stretching method for forming a biaxially stretched film, for example, a sequential biaxial stretching method, a blow molding method, a simultaneous biaxial stretching method, etc. may be cited. As a method for coating a resin, a roll coating method, a gravure coating method, an extrusion coating method, etc. may be cited.
[0042] Examples of the resin forming the substrate layer 1 include polyester, polyamide, polyolefin, epoxy resin, acrylic resin, fluorine-containing resin, polyurethane, silicone-containing resin, phenolic resin and the like, or modified products of these resins. In addition, the resin forming the substrate layer 1 may be a copolymer of these resins, or a modified product of the copolymer. Furthermore, it may be a mixture of these resins.
[0043] As the resin forming the base material layer 1, polyester and polyamide are preferably used among these.
[0044] As polyester, specifically, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, copolyester, etc. can be cited. In addition, as copolyester, copolyester with ethylene terephthalate as the main repeating unit can be cited. Specifically, copolymer polyester with ethylene terephthalate as the main repeating unit and polymerized with ethylene isophthalate (hereinafter abbreviated as polyethylene glycol (terephthalate / isophthalate)), polyethylene glycol (terephthalate / adipate), polyethylene glycol (terephthalate / sodium sulfoisophthalate), polyethylene glycol (terephthalate / sodium isophthalate), polyethylene glycol (terephthalate / phenyl-dicarboxylate), polyethylene glycol (terephthalate / decane dicarboxylate), etc. can be cited. These polyesters may be used alone or in combination of two or more.
[0045] In addition, specific examples of polyamides include aliphatic polyamides such as nylon 6, nylon 66, nylon 610, nylon 12, nylon 46, and copolymers of nylon 6 and nylon 66; hexamethylenediamine-isophthalic acid-terephthalic acid copolymer polyamides such as nylon 6I, nylon 6T, nylon 6IT, and nylon 6I6T (I represents isophthalic acid, and T represents terephthalic acid); and polyamides. Aromatic polyamides such as MXD6 (poly(m-xylylene adipamide)); alicyclic polyamides such as polyamide PACM6 (poly(bis(4-aminocyclohexyl)methane adipamide); polyamides obtained by copolymerizing a lactam component or an isocyanate component such as 4,4′-diphenylmethane-diisocyanate; polyesteramide copolymers as copolymers of a copolymerized polyamide and a polyester or a polyalkylene ether glycol; or polyetheresteramide copolymers; and copolymers thereof. These polyamides may be used alone or in combination of two or more.
[0046] The substrate layer 1 preferably comprises at least one of a polyester film, a polyamide film and a polyolefin film, preferably comprises at least one of a stretched polyester film, a stretched polyamide film and a stretched polyolefin film, more preferably comprises at least one of a stretched polyethylene terephthalate film, a stretched polybutylene terephthalate film, a stretched nylon film and a stretched polypropylene film, and further preferably comprises at least one of a biaxially stretched polyethylene terephthalate film, a biaxially stretched polybutylene terephthalate film, a biaxially stretched nylon film and a biaxially stretched polypropylene film.
[0047] The substrate layer 1 may be a single layer or may be composed of two or more layers. When the substrate layer 1 is composed of two or more layers, the substrate layer 1 may be a laminated body formed by laminating resin films using an adhesive or the like, or may be a laminated body of two or more resin films formed by co-extruding resins. In addition, the laminated body of two or more resin films formed by co-extruding resins may be used as the substrate layer 1 without being stretched, or may be formed by uniaxial stretching or biaxial stretching.
[0048] In the substrate layer 1, as specific examples of a laminate of two or more layers of resin films, there can be cited a laminate of a polyester film and a nylon film, a laminate of two or more layers of nylon films, a laminate of two or more layers of polyester films, etc., preferably a laminate of a stretched nylon film and a stretched polyester film, a laminate of two or more layers of stretched nylon films, and a laminate of two or more layers of stretched polyester films. For example, when the substrate layer 1 is a laminate of two layers of resin films, preferably a laminate of a polyester resin film and a polyester resin film, a laminate of a polyamide resin film and a polyamide resin film, or a laminate of a polyester resin film and a polyamide resin film, more preferably a laminate of a polyethylene terephthalate film and a polyethylene terephthalate film, a laminate of a nylon film and a nylon film, or a laminate of a polyethylene terephthalate film and a nylon film. Furthermore, since polyester resin is less likely to change color when, for example, an electrolyte solution adheres to the surface, when the base material layer 1 is a laminate of two or more resin films, the polyester resin film is preferably located as the outermost layer of the base material layer 1 .
[0049] When the substrate layer 1 is a laminate of two or more layers of resin films, the two or more layers of resin films can be laminated using an adhesive. As for the preferred adhesive, the same materials as the adhesives exemplified in the adhesive layer 2 described later can be cited. In addition, there is no particular restriction on the method for laminating two or more layers of resin films, and a known method can be adopted, for example, dry lamination, sandwich lamination, extrusion lamination, thermal lamination, etc. can be cited, and dry lamination is preferably cited. When laminating using dry lamination, a polyurethane adhesive is preferably used as an adhesive. At this time, as the thickness of the adhesive, for example, about 2 to 5 μm can be cited. In addition, a primer layer can also be formed on the resin film and laminated. The primer layer can cite the same materials as the adhesives exemplified in the adhesive layer 2 described later. At this time, as the thickness of the primer layer, for example, about 0.01 to 1.0 μm can be cited.
[0050] In addition, additives such as lubricants, flame retardants, anti-blocking agents, antioxidants, light stabilizers, tackifiers, and antistatic agents may be present on at least one of the surface and the interior of the base layer 1. The additives may be used alone or in combination of two or more.
[0051] In the present invention, from the viewpoint of improving the formability of the external packaging material for the storage device, it is preferred that a lubricant is present on the surface of the substrate layer 1. As a lubricant, there is no particular limitation, and an amide-based lubricant is preferably cited. As a specific example of an amide-based lubricant, for example, saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, hydroxymethylamides, saturated fatty acid bisamides, unsaturated fatty acid bisamides, fatty acid ester amides, aromatic bisamides, etc. can be cited. As a specific example of saturated fatty acid amides, lauramide, palmitamide, stearamide, behenamide, hydroxystearamide, etc. can be cited. As a specific example of unsaturated fatty acid amides, oleamide, erucamide, etc. can be cited. As a specific example of substituted amides, N-oleyl palmitamide, N-stearyl stearamide, N-stearyl oleamide, N-oleyl stearamide, N-stearyl erucamide, etc. can be cited. In addition, as a specific example of hydroxymethylamides, hydroxymethyl stearamide, etc. can be cited. Specific examples of saturated fatty acid bisamides include methylene bisstearamide, ethylene biscaprylamide, ethylene bislaurylamide, ethylene bisstearamide, ethylene bishydroxystearamide, ethylene bisbehenamide, hexamethylene bisstearamide, hexamethylene bisbehenamide, hexamethylene hydroxystearamide, N,N′-distearyl adipamide, N,N′-distearyl sebacamide, etc. Specific examples of unsaturated fatty acid bisamides include ethylene bisoleamide, ethylene biserucamide, hexamethylene bisoleamide, N,N′-dioleyl adipamide, N,N′-dioleyl sebacamide, etc. Specific examples of fatty acid ester amides include stearamide stearic acid ethyl ester, etc. In addition, specific examples of aromatic bisamides include m-xylylene bisstearamide, m-xylylene bishydroxystearamide, N,N′-distearyl isophthalamide, etc. The lubricants may be used alone or in combination of two or more.
[0052] When a lubricant is present on the surface of the substrate layer 1, its amount is not particularly limited, but is preferably about 3 mg / m 2 More preferably 4 to 15 mg / m 2 About 5 to 14 mg / m 2 about.
[0053] The lubricant present on the surface of the base layer 1 may be the lubricant contained in the resin constituting the base layer 1 that oozes out, or the lubricant may be formed by coating the surface of the base layer 1 .
[0054] The thickness of the substrate layer 1 is not particularly limited as long as it can function as a substrate, and can be, for example, about 3 to 50 μm, preferably about 10 to 35 μm. When the substrate layer 1 is a laminate of two or more resin films, the thickness of the resin films constituting each layer can be, for example, about 2 to 35 μm, preferably about 2 to 25 μm.
[0055] [Adhesive layer 2]
[0056] In the external packaging material for a power storage device of the present invention, the adhesive layer 2 is a layer provided between the base layer 1 and the barrier layer 3 as necessary in order to improve the adhesion between them.
[0057] The adhesive layer 2 is formed by an adhesive capable of bonding the substrate layer 1 to the barrier layer 3. The adhesive used to form the adhesive layer 2 is not limited, and any type of adhesive such as chemical reaction type, solvent evaporation type, hot melt type, hot pressing type, etc. can be used. In addition, it can be a two-liquid curing adhesive (two-liquid adhesive), a single-liquid curing adhesive (single-liquid adhesive), or a resin that is not accompanied by a curing reaction. In addition, the adhesive layer 2 can be a single layer or a multilayer.
[0058] As the adhesive component contained in the adhesive, specifically, polyesters such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, and copolymer polyesters can be listed; polyethers; polyurethanes; epoxy resins; phenolic resins; polyamides such as nylon 6, nylon 66, nylon 12, and copolymer polyamides; polyolefin resins such as polyolefins, cyclic polyolefins, acid-modified polyolefins, and acid-modified cyclic polyolefins; polyvinyl acetate; cellulose; (meth) acrylic resins; polyimides; polycarbonates; amino resins such as urea resins and melamine resins; rubbers such as chloroprene rubber, nitrile rubber, and styrene-butadiene rubber; silicone resins, etc. These adhesive components can be used alone or in combination of two or more. Among these adhesive components, polyurethane adhesives are preferably listed. In addition, these resins as bonding components can be used in combination with suitable curing agents to improve bonding strength. About the above-mentioned curing agent, according to the functional group possessed by the bonding component, select suitable material from polyisocyanates, multifunctional epoxy resins, polymers containing oxazoline groups, polyamine resins, acid anhydrides etc.
[0059] As the polyurethane adhesive, for example, a polyurethane adhesive comprising a main agent containing a polyol compound and a curing agent containing an isocyanate compound can be cited. Preferably, a two-liquid curing type polyurethane adhesive is cited, which uses a polyol such as polyester polyol, polyether polyol and acrylic polyol as a main agent and an aromatic or aliphatic polyisocyanate as a curing agent. In addition, as the polyol compound, a polyester polyol having a hydroxyl group in the side chain in addition to the hydroxyl group at the end of the repeating unit is preferably used. By forming the adhesive layer 2 with a polyurethane adhesive, it is possible to impart excellent electrolyte tolerance to the external packaging material for the storage device, and even if the electrolyte is attached to the side, it is possible to suppress the peeling of the substrate layer 1.
[0060] In addition, adhesive layer 2 allows the addition of other components as long as it does not hinder adhesion, and can contain coloring agent or thermoplastic elastomer, tackifier, filler, etc. By making adhesive layer 2 contain coloring agent, storage device can be colored with outer packaging material. As coloring agent, known materials such as pigment, dye can be used. In addition, coloring agent can only use 1 kind, also can use more than 2 kinds in a mixed manner.
[0061] The type of pigment is not particularly limited as long as it does not hinder the adhesion of the adhesive layer 2. Examples of organic pigments include azo pigments, phthalocyanine pigments, quinacridone pigments, anthraquinone pigments, dioxazine pigments, indigo-thioindigo pigments, perinone-perylene pigments, isoindolenine pigments, and benzimidazolone pigments; examples of inorganic pigments include carbon black pigments, titanium oxide pigments, cadmium pigments, lead pigments, chromium oxide pigments, and iron pigments; and examples of fine powder of mica and fish scale foil.
[0062] Among the colorants, carbon black is preferred in order to make the appearance of the external packaging material for an electric storage device black, for example.
[0063] The average particle size of the pigment is not particularly limited, and may be, for example, about 0.05 to 5 μm, preferably about 0.08 to 2 μm. The average particle size of the pigment is a median particle size measured by a laser diffraction / scattering particle size distribution measuring device.
[0064] The content of the pigment in the adhesive layer 2 is not particularly limited as long as the external packaging material for a power storage device can be colored, and is, for example, about 5 to 60% by mass, preferably 10 to 40% by mass.
[0065] The thickness of the adhesive layer 2 is not particularly limited as long as the base layer 1 and the barrier layer 3 can be bonded together. For example, the thickness may be about 1 μm or more, about 2 μm or more, or about 10 μm or less, or about 5 μm or less. The preferred range may be about 1 to 10 μm, about 1 to 5 μm, about 2 to 10 μm, or about 2 to 5 μm.
[0066] [Coloring Layer]
[0067] The colored layer is a layer (not shown) provided between the base layer 1 and the barrier layer 3 as required. When the adhesive layer 2 is provided, the colored layer may be provided between the base layer 1 and the adhesive layer 2, or between the adhesive layer 2 and the barrier layer 3. In addition, the colored layer may be provided outside the base layer 1. By providing the colored layer, the external packaging material for the power storage device can be colored.
[0068] The colored layer can be formed, for example, by applying an ink containing a colorant to the surface of the base layer 1, the surface of the adhesive layer 2, or the surface of the barrier layer 3. As the colorant, known materials such as pigments and dyes can be used. In addition, the colorant can be used alone or in combination of two or more.
[0069] Specific examples of the colorant contained in the colored layer include the same colorants as those described in the section of [Adhesive Layer 2].
[0070] [Barrier layer 3]
[0071] In the external packaging material for a power storage device, the barrier layer 3 is a layer that at least suppresses the intrusion of moisture.
[0072] As the barrier layer 3, for example, metal foil, vapor-deposited film, resin layer, etc. with barrier properties can be listed. As the vapor-deposited film, metal vapor-deposited film, inorganic oxide vapor-deposited film, carbon-containing inorganic oxide vapor-deposited film, etc. can be listed; as the resin layer, polyvinylidene chloride, polymers with chlorotrifluoroethylene (CTFE) as the main component, polymers with tetrafluoroethylene (TFE) as the main component, polymers with fluoroalkyl groups, and polymers with fluoroalkyl units as the main component, etc., fluororesins, ethylene-vinyl alcohol copolymers, etc. can be listed. In addition, as the barrier layer 3, resin films provided with at least one layer of these vapor-deposited films and resin layers can also be listed. The barrier layer 3 can be provided with multiple layers. The barrier layer 3 preferably includes a layer composed of a metal material. As the metal material constituting the barrier layer 3, specifically aluminum alloy, stainless steel, titanium steel, steel plate, etc. can be listed; when used in the form of metal foil, it is preferably included at least one of aluminum alloy foil and stainless steel foil.
[0073] Regarding aluminum alloy foil, from the perspective of improving the formability of the outer packaging material for a storage device, for example, a soft aluminum alloy foil composed of an annealed aluminum alloy or the like is more preferred; from the perspective of further improving the formability, an iron-containing aluminum alloy foil is preferred. In the iron-containing aluminum alloy foil (100% by mass), the iron content is preferably 0.1 to 9.0% by mass, and more preferably 0.5 to 2.0% by mass. By having an iron content of 0.1% or more by mass, an outer packaging material for a storage device with better formability can be obtained. By having an iron content of 9.0% or less by mass, an outer packaging material for a storage device with better flexibility can be obtained. Examples of soft aluminum alloy foil include aluminum alloy foils having compositions specified in JIS H4160: 1994A8021H-O, JIS H4160: 1994A8079H-O, JIS H4000: 2014A8021P-O, or JIS H4000: 2014A8079P-O. Silicon, magnesium, copper, manganese, etc. may be added as needed. Softening may be performed by annealing or the like.
[0074] In addition, examples of stainless steel foil include austenitic, ferritic, austenite-ferritic, martensitic, and precipitation hardened stainless steel foils. From the perspective of providing an external packaging material for a power storage device having better formability, the stainless steel foil is preferably made of austenitic stainless steel.
[0075] Specific examples of the austenitic stainless steel constituting the stainless steel foil include SUS304, SUS301, and SUS316L. Among these, SUS304 is particularly preferred.
[0076] Regarding the thickness of the barrier layer 3, when it is a metal foil, it can be used as long as it can function as a barrier layer that at least inhibits the intrusion of moisture, and for example, it can be about 9 to 200 μm. Regarding the thickness of the barrier layer 3, for example, the upper limit is preferably about 85 μm or less, more preferably about 50 μm or less, further preferably about 40 μm or less, and particularly preferably about 35 μm or less, and preferably about 10 μm or more, further preferably about 20 μm or more, and more preferably about 25 μm or more. As a preferred range of the thickness, about 10 to 85 μm, about 10 to 50 μm, about 10 to 40 μm, about 10 to 35 μm, about 20 to 85 μm, about 20 to 50 μm, about 20 to 40 μm, about 20 to 35 μm, about 25 to 85 μm, about 25 to 50 μm, about 25 to 40 μm, about 25 to 35 μm, about 25 to 85 μm, about 25 to 50 μm, about 25 to 40 μm, and about 25 to 35 μm. When the barrier layer 3 is composed of an aluminum alloy foil, the above range is particularly preferred. In particular, when the barrier layer 3 is made of a stainless steel foil, the thickness of the stainless steel foil is preferably about 60 μm or less, more preferably about 50 μm or less, further preferably about 40 μm or less, further preferably about 30 μm or less, and particularly preferably about 25 μm or less, and preferably about 10 μm or more, more preferably about 15 μm or more. Preferred thickness ranges include about 10 to 60 μm, about 10 to 50 μm, about 10 to 40 μm, about 10 to 30 μm, about 10 to 25 μm, about 15 to 60 μm, about 15 to 50 μm, about 15 to 40 μm, about 15 to 30 μm, and about 15 to 25 μm.
[0077] In addition, when the barrier layer 3 is a metal foil, in order to prevent dissolution or corrosion, it is preferred that at least the surface on the opposite side of the substrate layer has a corrosion-resistant film. The barrier layer 3 may also have a corrosion-resistant film on both sides. Among them, the corrosion-resistant film refers to a film that makes the barrier layer corrosion-resistant (for example, acid resistance, alkali resistance, etc.) by, for example, performing hot water deterioration treatment such as boehm film treatment, chemical surface treatment, anodizing treatment, plating treatment of nickel or chromium, etc., and anti-corrosion treatment of coating agent on the surface of the barrier layer. The corrosion-resistant film specifically refers to a film that improves the acid resistance of the barrier layer (acid-resistant film), a film that improves the alkali resistance of the barrier layer (alkali-resistant film), etc. As a treatment for forming a corrosion-resistant film, one type can be performed, or two or more types can be combined. In addition, it is also possible to perform multiple layers instead of just one layer. In addition, among these treatments, hot water deterioration treatment and anodizing treatment are treatments that use a treatment agent to dissolve the surface of the metal foil to form a metal compound with excellent corrosion resistance. Among them, these treatments are sometimes also included in the definition of chemical surface treatment. When the barrier layer 3 has a corrosion-resistant film, the corrosion-resistant film is included in the barrier layer 3 .
[0078] The corrosion-resistant film exhibits the following effects during the molding of the exterior material for the storage device: preventing delamination between the barrier layer (e.g., aluminum alloy foil) and the substrate layer, preventing the surface of the barrier layer from being dissolved and corroded by hydrogen fluoride generated by the reaction between the electrolyte and water, especially when the barrier layer is an aluminum alloy foil, preventing the aluminum oxide present on the surface of the barrier layer from being dissolved and corroded, and improving the adhesion (wettability) of the barrier layer surface, preventing delamination between the substrate layer and the barrier layer during heat sealing, and preventing delamination between the substrate layer and the barrier layer during molding.
[0079] As corrosion-resistant films formed by chemical surface treatment, various films are known, and corrosion-resistant films containing at least one of phosphates, chromates, fluorides, triazine thiol compounds and rare earth oxides can be mainly listed. As chemical surface treatment using phosphates and chromates, for example, chromic acid chromate treatment, phosphoric acid chromate treatment, phosphoric acid-chromate treatment, chromate treatment, etc. can be listed, and as chromium compounds used in these treatments, for example, chromium nitrate, chromium fluoride, chromium sulfate, chromium acetate, chromium oxalate, chromium dihydrogen phosphate, chromic acid acetoacetate, chromium chloride, potassium chromium sulfate, etc. can be listed. In addition, as phosphorus compounds used in these treatments, sodium phosphate, potassium phosphate, ammonium phosphate, polyphosphoric acid, etc. can be listed. In addition, as chromate treatment, etching chromate treatment, electrolytic chromate treatment, coating type chromate treatment, etc. can be listed, and coating type chromate treatment is preferred. The coating type chromate treatment is a treatment as follows: first, the surface of at least the inner layer side of the barrier layer (for example, aluminum alloy foil) is degreased by a known treatment method such as an alkali immersion method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, an acid activation method, etc., and then, a treatment liquid containing a phosphate metal salt such as Cr (chromium) phosphate, Ti (titanium) phosphate, Zr (zirconium) phosphate, Zn (zinc) phosphate, and a mixture of these metal salts as a main component, or a treatment liquid containing a phosphate nonmetallic salt and a mixture of these nonmetallic salts as a main component, or a treatment liquid composed of a mixture of these and a synthetic resin, etc., is applied to the degreased surface by a known coating method such as a roll coating method, a gravure printing method, a dipping method, etc., and then dried. The treatment liquid can be various solvents such as water, an alcohol solvent, a hydrocarbon solvent, a ketone solvent, an ester solvent, an ether solvent, etc., preferably water. In addition, as the resin component used at this time, polymers such as phenolic resins or acrylic resins can be listed, and chromate treatment using an amino-phenolic polymer having repeating units represented by the following general formulas (1) to (4) can be listed. Among them, in the amino-phenolic polymer, the repeating units represented by the following general formulas (1) to (4) can contain one type alone, or can be any combination of two or more types. The acrylic resin is preferably polyacrylic acid, acrylic acid methacrylate copolymer, acrylic acid maleic acid copolymer, acrylic acid styrene copolymer or their sodium salts, ammonium salts, amine salts and other derivatives. Particularly preferred are derivatives of polyacrylic acid such as ammonium salts, sodium salts or amine salts of polyacrylic acid. In the present invention, polyacrylic acid means a polymer of acrylic acid. In addition, the acrylic resin is also preferably a copolymer of acrylic acid and dicarboxylic acid or dicarboxylic anhydride, and is also preferably an ammonium salt, sodium salt or amine salt of a copolymer of acrylic acid and dicarboxylic acid or dicarboxylic anhydride. The acrylic resin can be used alone or in combination of two or more.
[0080]
[0081]
[0082] In the general formulae (1) to (4), X represents a hydrogen atom, a hydroxyl group, an alkyl group, a hydroxyalkyl group, an allyl group or a benzyl group. 1 and R 2 are the same as or different from each other and represent a hydroxyl group, an alkyl group or a hydroxyalkyl group. 1 and R 2 The alkyl group represented by , for example, can be a linear or branched alkyl group having 1 to 4 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, and tert-butyl. 1 and R 2 The hydroxyalkyl group represented by the above-mentioned group includes, for example, hydroxymethyl, 1-hydroxyethyl, 2-hydroxyethyl, 1-hydroxypropyl, 2-hydroxypropyl, 3-hydroxypropyl, 1-hydroxybutyl, 2-hydroxybutyl, 3-hydroxybutyl, 4-hydroxybutyl, and other linear or branched alkyl groups having 1 to 4 carbon atoms substituted with one hydroxyl group. 1 and R 2 The alkyl and hydroxyalkyl groups shown may be the same as or different from each other. In the general formulae (1) to (4), X is preferably a hydrogen atom, a hydroxyl group or a hydroxyalkyl group. The number average molecular weight of the aminophenolic polymer having repeating units shown in the general formulae (1) to (4) is, for example, preferably about 5 to 1,000,000, and more preferably about 1,000 to 20,000. For example, a phenol compound or a naphthol compound is polycondensed with formaldehyde to produce a polymer composed of repeating units shown in the general formula (1) or (3), and then, formaldehyde and an amine (R 1 R 2 NH) will be functional group (-CH2NR 1 R 2 ) is introduced into the polymer obtained above to produce an aminated phenol polymer. The aminated phenol polymer can be used alone or in combination of two or more.
[0083] As other examples of corrosion-resistant films, films formed by coating a coating-type anti-corrosion treatment containing at least one coating agent selected from rare earth oxide sol, anionic polymers, and cationic polymers can be cited. The coating agent can also contain phosphoric acid or phosphates, and a cross-linking agent that cross-links the polymer. Rare earth oxide sol is obtained by dispersing microparticles of rare earth oxide (for example, particles with an average particle size of less than 100nm) in a liquid dispersion medium. As rare earth oxides, cerium oxide, yttrium oxide, neodymium oxide, lanthanum oxide, etc. can be cited. From the perspective of further improving adhesion, cerium oxide is preferred. The rare earth oxides contained in the corrosion-resistant film can be used alone or in combination of two or more. As the liquid dispersion medium of the rare earth oxide sol, various solvents such as water, alcohol solvents, hydrocarbon solvents, ketone solvents, ester solvents, and ether solvents can be used, preferably water. As cationic polymers, for example, polyethyleneimine, ionic polymer complexes composed of polyethyleneimine and polymers having carboxylic acids, primary amine grafted acrylic resins formed by graft polymerization of primary amines with acrylic acid main skeletons, polyallylamine or its derivatives, aminophenols, etc. are preferred. In addition, as anionic polymers, poly(methyl)acrylic acid or its salts, or copolymers with (methyl)acrylic acid or its salts as main components are preferred. In addition, the crosslinking agent is preferably selected from at least one of a compound having any functional group among isocyanate group, glycidyl group, carboxyl group, oxazoline group and a silane coupling agent. In addition, the above-mentioned phosphoric acid or phosphate is preferably condensed phosphoric acid or condensed phosphate.
[0084] An example of the corrosion-resistant film is a film formed by coating the surface of the barrier layer with a dispersion of fine particles of a metal oxide such as aluminum oxide, titanium oxide, cerium oxide, tin oxide, or barium sulfate dispersed in phosphoric acid and baking the dispersion at 150° C. or higher.
[0085] If necessary, the corrosion-resistant film may be formed into a laminated structure in which at least one of a cationic polymer and an anionic polymer is further laminated. Examples of the cationic polymer and the anionic polymer include the above-mentioned compounds.
[0086] Here, the composition analysis of the corrosion-resistant film can be performed by, for example, time-of-flight secondary ion mass spectrometry.
[0087] In the chemical surface treatment, there is no particular limitation on the amount of the corrosion-resistant film formed on the surface of the barrier layer 3. For example, in the case of a coating-type chromate treatment, it is preferred that the amount of the corrosion-resistant film formed on the surface of the barrier layer 3 is 100%. 2On the surface, the content ratio of the chromic acid compound is, for example, about 0.5 to 50 mg, preferably about 1.0 to 40 mg, calculated as chromium, the content ratio of the phosphorus compound is, for example, about 0.5 to 50 mg, preferably about 1.0 to 40 mg, calculated as phosphorus, and the content ratio of the amino-phenolic polymer is, for example, about 1.0 to 200 mg, preferably about 5.0 to 150 mg.
[0088] There is no particular limitation on the thickness of the corrosion-resistant film. From the perspective of the cohesive force of the film and the adhesion with the barrier layer or the heat-fusible resin layer, a thickness of about 1 nm to 20 μm is preferred, about 1 nm to 100 nm is more preferred, and about 1 nm to 50 nm is further preferred. The thickness of the corrosion-resistant film can be measured by observation using a transmission electron microscope or by a combination of observation using a transmission electron microscope and energy dispersive X-ray spectroscopy or electron beam energy loss spectroscopy. By performing a composition analysis of the corrosion-resistant film using time-of-flight secondary ion mass spectrometry, secondary ions (e.g., Ce2PO4 + 、CePO4 - At least one of the above), for example, secondary ions composed of Cr, P and O (such as CrPO2 + 、CrPO4 - At least one of the above (etc.) peaks.
[0089] The chemical surface treatment can be performed in the following manner: after applying a solution containing a compound for forming a corrosion-resistant film to the surface of the barrier layer by a rod coating method, a roller coating method, a gravure coating method, a dipping method, etc., the barrier layer is heated so that the temperature reaches about 70 to 200°C. In addition, before the barrier layer is subjected to the chemical surface treatment, the barrier layer may be degreased in advance by an alkali dipping method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, etc. By performing the degreasing treatment in this way, the surface of the barrier layer can be more effectively chemically surface treated. In addition, by using an acid degreasing agent obtained by dissolving a fluorine-containing compound using an inorganic acid in the degreasing treatment, not only can the degreasing effect of the metal foil be obtained, but also a passive metal fluoride can be formed. In this case, only the degreasing treatment may be performed.
[0090] [Thermal Fusible Resin Layer 4]
[0091] In the external packaging material for a storage device of the present invention, the heat-fusible resin layer 4 corresponds to the innermost layer, and is a layer (sealing layer) that performs the function of sealing the storage device element by heat-fusion when assembling the storage device. In the external packaging material 10 for a storage device of the present invention, the heat-fusible resin layer 4 is composed of a single layer or multiple layers, and in the heat-fusible resin layer 4, the first heat-fusible resin layer 41 constitutes the surface of the laminate. Therefore, when assembling the storage device, the first heat-fusible resin layer 41 is heat-fused to seal the storage device element.
[0092] When the thermally adhesive resin layer 4 is composed of a single layer, the thermally adhesive resin layer 4 constitutes a first thermally adhesive resin layer 41 . Figure 1 and Figure 2 The laminated structure in which the thermally fusible resin layer 4 is composed of a single layer of the first thermally fusible resin layer 41 and the first thermally fusible resin layer 41 constitutes the surface of the laminated body is shown.
[0093] When the heat-fusible resin layer 4 is composed of a plurality of layers, it includes at least a first heat-fusible resin layer 41 and a second heat-fusible resin layer 42 in this order from the surface side of the laminate constituting the power storage device exterior material 10 . Figure 3 to Figure 5 The laminated structure is shown in which the thermally fusible resin layer 4 is composed of a plurality of layers (two layers) of a first thermally fusible resin layer 41 and a second thermally fusible resin layer 42, and the first thermally fusible resin layer 41 constitutes the surface of the laminated body.
[0094] When the heat-fusible resin layer 4 is composed of multiple layers, the heat-fusible resin layer 4 may include a third heat-fusible resin layer, a fourth heat-fusible resin layer, etc. on the barrier layer 3 side of the second heat-fusible resin layer 42 in addition to the first heat-fusible resin layer 41 and the second heat-fusible resin layer 42. When the heat-fusible resin layer 4 is composed of multiple layers, it is preferred that the heat-fusible resin layer 4 is composed of two layers, namely, the first heat-fusible resin layer 41 and the second heat-fusible resin layer 42.
[0095] The external packaging material for a power storage device of the present invention is characterized in that the first heat-fusible resin layer 41 has a logarithmic decrement ΔE of 0.20 or less at 140° C. in a rigid body oscillator measurement. In the present invention, by making the logarithmic decrement ΔE at 140° C. 0.20 or less, the first heat-fusible resin layer 41 can be effectively prevented from being destroyed during heat fusion.
[0096] The logarithmic decrement at 140°C in the rigid body oscillator measurement is an indicator of the hardness of the resin in a high temperature environment of 140°C. The smaller the logarithmic decrement, the higher the hardness of the resin. When the temperature at which the heat-fusible resin layer is heat-fused is high, the heat-fusible resin layer may protrude significantly toward the inside of the heat-fusible portion (the side of the space for storing the storage device element) at the heat-fusible portion formed by heat-fusion of the heat-fusible resin layer. Once the heat-fusible resin layer 4 protrudes significantly toward the inside of the heat-fusible portion, cracks may appear in the heat-fusible resin layer 4 starting from the protruding portion (the so-called polymer aggregation), and the insulation property is likely to decrease. Fig.11 The schematic cross-sectional view shows a protrusion A formed inside the heat-welding portion of the heat-welding resin layer 4. As shown in the cross-sectional view, the protrusion A has endpoints A1 and A2, and these endpoints A1 and A2 are structurally prone to become the starting points of cracks. Therefore, once the heat-welding resin layer 4 protrudes significantly inside the heat-welding portion to form a protrusion, the insulation will decrease due to the cracks. Therefore, it is very important to control the shape of the heat-welding portion, and for this purpose, the hardness of the heat-welding resin layer at high temperature is very important. Therefore, the logarithmic attenuation rate at a high temperature of 140°C is used in the present invention. In the rigid vibrator measurement, the attenuation rate of the vibrator is measured when the temperature of the resin is increased from a low temperature to a high temperature. In the rigid vibrator measurement, the edge portion is usually brought into contact with the surface of the object to be measured, and the vibrator is moved in the left and right directions to apply vibration to the object to be measured. In the external packaging material for a storage device of the present invention, by disposing a hard first heat-fusible resin layer 41 having a logarithmic decrement of 0.20 or less in a high-temperature environment of 140°C on the surface of the external packaging material for a storage device, it is possible to suppress the first heat-fusible resin layer 41 from being destroyed (thinning) during heat-fusion bonding of the external packaging material for a storage device. By suppressing the destruction of the first heat-fusible resin layer 41, it is possible to effectively suppress the heat-fusible resin layer from significantly protruding inside the heat-fusion bonded portion formed by heat-fusion bonding the heat-fusible resin layer, and it is possible to effectively suppress the reduction in the insulation properties of the external packaging material for a storage device due to heat-fusion bonding.
[0097] The logarithmic attenuation rate ΔE is calculated by the following formula.
[0098] ΔE=[ln(A1 / A2)+ln(A2 / A3)+···ln(An / An+1)] / nA: Amplitude
[0099] n: wave number
[0100] In the external packaging material for the storage device of the present invention, from the viewpoint of effectively suppressing the destruction of the first heat-fusible resin layer 41 when the first heat-fusible resin layer 41 is heat-fused, the logarithmic decay rate ΔE at 140°C is preferably about 0.10 or more, more preferably about 0.11 or more, and further preferably about 0.12 or more, and is preferably about 0.18 or less, more preferably about 0.15 or less, and further preferably about 0.13 or less. Preferred ranges include about 0.10 to 0.20, about 0.10 to 0.18, about 0.10 to 0.15, about 0.10 to 0.13, about 0.11 to 0.20, about 0.11 to 0.18, about 0.11 to 0.15, about 0.11 to 0.13, about 0.12 to 0.20, about 0.12 to 0.18, about 0.12 to 0.15, and about 0.12 to 0.13.
[0101] In addition, in the external packaging material for a storage device of the present invention, from the viewpoint of effectively suppressing the destruction of the first heat-fusible resin layer 41 when the first heat-fusible resin layer 41 is heat-fused, in the external packaging material for a storage device of the present invention, the logarithmic decrement rate ΔE of the first heat-fusible resin layer 41 at 80°C in a rigid body oscillator measurement is preferably greater than 0.08, more preferably about 0.09 or more, and further preferably about 0.10 or more. In addition, in the external packaging material for a storage device of the present invention, the logarithmic decrement rate ΔE of the first heat-fusible resin layer 41 at 80°C in a rigid body oscillator measurement is preferably about 0.20 or less, more preferably about 0.18 or less, and further preferably about 0.15 or less. The preferred range of the logarithmic decay rate ΔE is greater than 0.08 and less than 0.20, greater than 0.08 and less than 0.18, greater than 0.08 and less than 0.15, approximately 0.09 to 0.20, approximately 0.09 to 0.18, approximately 0.09 to 0.15, approximately 0.10 to 0.20, approximately 0.10 to 0.18, and approximately 0.10 to 0.15.
[0102] The logarithmic attenuation ΔE of the first heat-fusible resin layer 41 at 80°C in the rigid body oscillator measurement is measured in the same manner as the logarithmic attenuation ΔE at 140°C measurement method above, except that the logarithmic attenuation ΔE is measured when the surface temperature of the first heat-fusible resin layer 41 reaches 80°C.
[0103] The logarithmic decrement ΔE of the first heat-fusible resin layer 41 can be adjusted by, for example, the melt flow rate (MFR), molecular weight, melting point, softening point, molecular weight distribution, degree of crystallinity, etc. of the resin constituting the first heat-fusible resin layer 41 .
[0104] In the measurement of the logarithmic decrement ΔE, a commercially available rigid oscillator model physical property tester was used to perform a rigid oscillator physical property test on the first heat-fusible resin layer 41 under the conditions of using a cylindrical cylinder edge as the edge portion pressed on the first heat-fusible resin layer 41, an initial amplitude of 0.3 degrees, and a temperature increase rate of 3°C / minute in the temperature range of 30°C to 200°C. Thus, the standard for suppressing the destruction of the first heat-fusible resin layer 41 described later was defined based on the logarithmic decrement at 140°C. Among them, for the first heat-fusible resin layer 41 for which the logarithmic decrement ΔE was measured, the sample after the external packaging material for the storage device was immersed in 15% hydrochloric acid and the base material layer and the aluminum foil were dissolved and fully dried, and the sample was used as the measurement object. When the external packaging material for the storage device has the adhesive layer 5 described later, a laminate of the adhesive layer 5 and the heat-fusible resin layer 4 was used as a sample.
[0105] Alternatively, a storage device packaging material may be obtained from the storage device to measure the logarithmic decrement ΔE of the first heat-fusible resin layer 41. When the storage device packaging material is obtained from the storage device to measure the logarithmic decrement ΔE of the first heat-fusible resin layer 41, a sample is cut from the top portion of the storage device packaging material that is not elongated by molding and used as the measurement object.
[0106] In addition, in the external packaging material for a storage device of the present invention, after the heat-fusible resin layers constituting the laminated body of the storage device external packaging material are heated and pressed in the lamination direction under the conditions of a temperature of 190° C., a surface pressure of 2.0 MPa, and a time of 3 seconds, the residual ratio of the total thickness of the two first heat-fusible resin layers 41 is preferably about 30% or more, more preferably about 32% or more, and further preferably about 34% or more. As preferred ranges, 30 to 60%, 32 to 60%, 34 to 60%, 30 to 50%, 32 to 50%, and 34 to 50% can be listed. In addition, the upper limit of the residual ratio of the thickness is, for example, about 60% or about 50%. The residual ratio of the thickness is a value measured by the following method. In order to set the residual ratio of the thickness, for example, the type, composition, molecular weight, etc. of the resin constituting the first heat-fusible resin layer 41 can be listed.
[0107] <Measurement of Remaining Ratio of Thickness of First Thermally Fusible Resin Layer>
[0108] The external packaging material for the storage device is cut into a length of 150 mm × a width of 60 mm to prepare a test sample. Next, the first heat-fusible resin layers 41 of the test sample are made to face each other. Next, in this state, a metal plate with a width of 7 mm is used to heat and pressurize the test sample from both sides in the stacking direction at a temperature of 190°C, a surface pressure of 0.5 MPa, and a time of 3 seconds to heat-fuse the first heat-fusible resin layers 41. Next, the heat-fused portion of the test sample is cut in the stacking direction using a slicer, and the total thickness of the two first heat-fusible resin layers 41 that are heat-fused to each other is measured for the exposed cross section. The same operation is performed on the test sample before heat-fusing, and the sample is cut in the stacking direction using a slicer, and the thickness of the two first heat-fusible resin layers 41 is measured for the exposed cross section. The ratio of the total thickness of the two first heat-fusible resin layers 41 after heat-fusion bonding to the total thickness of the two first heat-fusible resin layers 41 before heat-fusion bonding is calculated, and the remaining ratio (%) of the total thickness of the two first heat-fusible resin layers 41 is measured. The thickness of the two first heat-fusible resin layers 41 in the heat-fusion portion is measured at a portion where the thickness of the external packaging material for a storage device is constant.
[0109] Alternatively, the external packaging material for a storage device may be obtained from the storage device to measure the remaining ratio of the total thickness of the two first heat-fusible resin layers 41. When the external packaging material for a storage device is obtained from the storage device to measure the remaining ratio of the total thickness of the two first heat-fusible resin layers 41, a sample is cut from the top surface of the external packaging material for a storage device that is not elongated by molding, and used as a measurement object.
[0110] The resin constituting the first heat-fusible resin layer 41 is not particularly limited as long as it can be heat-fused and the logarithmic decrement ΔE of the first heat-fusible resin layer 41 is 0.20 or less.
[0111] As the resin constituting the first heat-fusible resin layer 41, a resin containing a polyolefin skeleton, such as polyolefin or acid-modified polyolefin, is preferred. The fact that the resin constituting the first heat-fusible resin layer 41 contains a polyolefin skeleton can be analyzed, for example, by infrared spectroscopy, gas chromatography-mass spectrometry, or the like. In addition, when analyzing the resin constituting the first heat-fusible resin layer 41 by infrared spectroscopy, it is preferred to detect a peak derived from maleic anhydride. For example, when measuring maleic anhydride-modified polyolefin by infrared spectroscopy, a peak at a wave number of 1760 cm -1 Nearby and wave number 1780cm -1 A peak derived from maleic anhydride is detected near the first heat-fusible resin layer 41. When the first heat-fusible resin layer 41 is a layer composed of maleic anhydride-modified polyolefin, a peak derived from maleic anhydride is detected when measured by infrared spectroscopy. However, when the acid modification degree is low, the peak sometimes becomes smaller and cannot be detected. In this case, nuclear magnetic resonance spectroscopy can be used for analysis.
[0112] As polyolefins, specifically, polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene can be listed; ethylene-α-olefin copolymers; polypropylenes such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); propylene-α-olefin copolymers; terpolymers of ethylene-butene-propylene, etc. Among these, polypropylene is preferred. The polyolefin resin in the copolymer can be a block copolymer or a random copolymer. These polyolefin resins can be used alone or in combination of two or more.
[0113] In addition, the polyolefin may also be a cyclic polyolefin. Cyclic polyolefin is a copolymer of an olefin and a cyclic monomer. As the olefin constituting the above-mentioned cyclic polyolefin, for example, ethylene, propylene, 4-methyl-1-pentene, styrene, butadiene, isoprene, etc. can be cited. In addition, as the cyclic monomer constituting the cyclic polyolefin, for example, cyclic olefins such as norbornene can be cited; cyclic dienes such as cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norbornene, etc., can be cited. Among these, cyclic olefins are preferably cited, and norbornene is further preferably cited.
[0114] Acid-modified polyolefin is a polymer obtained by block polymerization or graft polymerization of polyolefin using an acid component. As the acid-modified polyolefin, the above-mentioned polyolefin, a copolymer obtained by copolymerizing the above-mentioned polyolefin with a polar molecule such as acrylic acid or methacrylic acid, or a polymer such as a cross-linked polyolefin can also be used. In addition, as the acid component used for acid modification, for example, carboxylic acids or anhydrides thereof such as maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, and itaconic anhydride can be cited.
[0115] The acid-modified polyolefin may also be an acid-modified cyclic polyolefin. The acid-modified cyclic polyolefin is a polymer obtained by copolymerizing a part of the monomers constituting the cyclic polyolefin with an acid component, or a polymer obtained by block polymerization or graft polymerization of the acid component and the cyclic polyolefin. The acid-modified cyclic polyolefin is the same as above. In addition, the acid component used for the acid modification is the same as the acid component used for the modification of the above-mentioned polyolefin.
[0116] Preferred examples of the acid-modified polyolefin include polyolefin modified with carboxylic acid or its anhydride, polypropylene modified with carboxylic acid or its anhydride, maleic anhydride-modified polyolefin, and maleic anhydride-modified polypropylene.
[0117] The first thermally fusible resin layer 41 may be formed of a single resin or a blended polymer in which two or more resins are combined.
[0118] The first heat-fusible resin layer 41 constituting the surface preferably contains polyolefin. For example, in the storage device exterior material 10 of the present invention, when the heat-fusible resin layer 4 has the first heat-fusible resin layer 41 and the second heat-fusible resin layer 42, it is preferred that the first heat-fusible resin layer 41 constituting the surface contains polyolefin, and the second heat-fusible resin layer 42 contains acid-modified polyolefin. In addition, in the storage device exterior material 10 of the present invention, when there is an adhesive layer 5, it is preferred that the first heat-fusible resin layer 41 constituting the surface contains polyolefin, and the adhesive layer 5 contains acid-modified polyolefin. In addition, it is preferred that the adhesive layer 5 contains acid-modified polyolefin, the first heat-fusible resin layer contains polyolefin, and the second heat-fusible resin layer contains polyolefin, and it is more preferred that the adhesive layer 5 contains acid-modified polypropylene, the first heat-fusible resin layer contains polypropylene, and the second heat-fusible resin layer contains polypropylene.
[0119] In addition, the first heat-fusible resin layer 41 may contain a lubricant or the like as needed. When the first heat-fusible resin layer 41 contains a lubricant, the moldability of the external packaging material for the storage device can be improved. There is no particular limitation on the lubricant, and a known lubricant can be used. One lubricant may be used alone, or two or more lubricants may be used in combination.
[0120] The lubricant is not particularly limited, but preferably an amide-based lubricant is used. Specific examples of the lubricant include the lubricants exemplified for the substrate layer 1. The lubricant may be used alone or in combination of two or more.
[0121] When a lubricant is present on the surface of the first heat-fusible resin layer 41, the amount of the lubricant is not particularly limited, but from the viewpoint of improving the moldability of the external packaging material for a storage device, 10 to 50 mg / m 2 About 15 to 40 mg / m 2 When a lubricant is present on the surface of the first heat-fusible resin layer 41 , the first heat-fusible resin layer 41 constitutes the surface of the power storage device exterior material 10 including the lubricant.
[0122] The lubricant present on the surface of the first heat-fusible resin layer 41 may be the lubricant contained in the resin constituting the first heat-fusible resin layer 41 seeping out, or the lubricant may be applied to the surface of the first heat-fusible resin layer 41 .
[0123] The thickness of the first heat-fusible resin layer 41 is not particularly limited as long as the heat-fusible resin layer performs a function of sealing the power storage device element by heat-fusion.
[0124] From the viewpoint of effectively suppressing the first heat-fusible resin layer 41 from being destroyed during heat fusion, the thickness of the first heat-fusible resin layer 41 is preferably about 100 μm or less, about 85 μm or less, or about 60 μm or less, and may be 5 μm or more, 10 μm or more, 20 μm or more, 30 μm or more, or 40 μm or more. Preferred ranges include about 5 to 100 μm, about 5 to 85 μm, about 5 to 60 μm, about 10 to 100 μm, about 10 to 85 μm, about 10 to 60 μm, about 20 to 100 μm, about 20 to 85 μm, about 20 to 60 μm, about 30 to 100 μm, about 30 to 85 μm, about 30 to 60 μm, about 40 to 100 μm, about 40 to 85 μm, or about 40 to 60 μm.
[0125] Specifically, from the viewpoint of effectively suppressing the destruction of the first heat-fusible resin layer 41 during heat welding, when the heat-fusible resin layer 4 is composed of a single layer of the first heat-fusible resin layer 41, the thickness of the first heat-fusible resin layer 41 is preferably about 100 μm or less, about 85 μm or less, about 60 μm or less, about 25 μm or less, and may be 5 μm or more, 10 μm or more, 20 μm or more, 30 μm or more, or 40 μm or more. Preferred ranges include about 5 to 100 μm, about 5 to 85 μm, about 5 to 60 μm, about 5 to 25 μm, about 10 to 100 μm, about 10 to 85 μm, about 10 to 60 μm, about 10 to 25 μm, about 20 to 100 μm, about 20 to 85 μm, about 20 to 60 μm, about 20 to 25 μm, about 30 to 100 μm, about 30 to 85 μm, about 30 to 60 μm, about 40 to 100 μm, about 40 to 85 μm, and about 40 to 60 μm.
[0126] In addition, from the viewpoint of effectively suppressing the destruction of the first heat-fusible resin layer 41 during heat-fusion and improving the sealing property of the external packaging material for the storage device, when the heat-fusible resin layer 4 has the first heat-fusible resin layer 41 and the second heat-fusible resin layer 42, the thickness of the first heat-fusible resin layer 41 is preferably about 85 μm or less, about 60 μm or less, or about 25 μm or less, and may be 5 μm or more, 10 μm or more, 20 μm or more, 30 μm or more, or 40 μm or more. Preferred ranges include about 5 to 85 μm, about 5 to 60 μm, about 5 to 25 μm, about 10 to 85 μm, about 10 to 60 μm, about 10 to 25 μm, about 20 to 85 μm, about 20 to 60 μm, about 20 to 25 μm, about 30 to 85 μm, about 30 to 60 μm, about 40 to 85 μm, and about 40 to 60 μm.
[0127] When the heat-fusible resin layer 4 has a second heat-fusible resin layer 42, the resin constituting the second heat-fusible resin layer 42 is preferably a resin containing a polyolefin skeleton, such as a polyolefin, an acid-modified polyolefin, etc. These resins are the same as the resins described for the first heat-fusible resin layer 41. The resin constituting the second heat-fusible resin layer 42 contains a polyolefin skeleton, which can be analyzed by, for example, infrared spectroscopy, gas chromatography-mass spectrometry, etc. In addition, when analyzing the resin constituting the second heat-fusible resin layer 42 by infrared spectroscopy, it is preferred to detect the peak derived from maleic anhydride. For example, when measuring maleic anhydride-modified polyolefin by infrared spectroscopy, at a wave number of 1760 cm -1 Nearby and wave number 1780cm -1 A peak derived from maleic anhydride is detected near the second heat-fusible resin layer 42. When the second heat-fusible resin layer 42 is a layer composed of maleic anhydride-modified polyolefin, a peak derived from maleic anhydride is detected when measured by infrared spectroscopy. However, when the acid modification degree is low, the peak sometimes becomes smaller and cannot be detected. In this case, nuclear magnetic resonance spectroscopy can be used for analysis.
[0128] The second heat-fusible resin layer 42 preferably contains polyolefin. In particular, when the heat-fusible resin layer 4 has the first heat-fusible resin layer 41 and the second heat-fusible resin layer 42, and has the adhesive layer 5 described later, the second heat-fusible resin layer 42 preferably contains polyolefin. In addition, as described above, in the external packaging material 10 for a storage battery device of the present invention, when the heat-fusible resin layer 4 has the first heat-fusible resin layer 41 and the second heat-fusible resin layer 42, and does not have the adhesive layer 5 described later, it is preferred that the first heat-fusible resin layer 41 constituting the surface contains polyolefin, and the second heat-fusible resin layer 42 contains acid-modified polyolefin.
[0129] The thickness of the second heat-fusible resin layer 42 is not particularly limited as long as the heat-fusible resin layer 42 performs a function of sealing the power storage device element by heat-fusion.
[0130] From the viewpoint of effectively suppressing the first heat-fusible resin layer 41 from being destroyed during heat-fusion and improving the sealing property of the external packaging material for a storage device, the thickness of the second heat-fusible resin layer 42 is preferably greater than the thickness of the first heat-fusible resin layer 41. In order to achieve excellent heat-fusion property, the first heat-fusible resin layer 41 is preferably made of a resin that easily flows at high temperatures. By having such a thickness relationship, the first heat-fusible resin layer 41, which is a part of the heat-fusible resin layer 4 and is made of a resin that easily flows, can be made thinner, thereby improving the insulation property of the external packaging material for a storage device. By appropriately adjusting the MFR, melting point, molecular weight, etc. of the resin that constitutes the first heat-fusible resin layer 41, the first heat-fusible resin layer 41 can be made into a resin layer that easily flows at high temperatures.
[0131] From the viewpoint of effectively suppressing the first heat-fusible resin layer 41 from being destroyed during heat-fusion and improving the sealing property of the external packaging material for the storage device, the thickness of the second heat-fusible resin layer 42 is preferably about 100 μm or less, about 85 μm or less, about 60 μm or less, and may be 5 μm or more, 10 μm or more, 20 μm or more, 30 μm or more, or 40 μm or more. As a preferred range, about 5 to 100 μm, about 5 to 85 μm, about 5 to 60 μm, about 10 to 100 μm, about 10 to 85 μm, about 10 to 60 μm, about 20 to 100 μm, about 20 to 85 μm, about 20 to 60 μm, about 30 to 100 μm, about 30 to 85 μm, about 30 to 60 μm, about 40 to 100 μm, about 40 to 85 μm, or about 40 to 60 μm.
[0132] The heat-fusible resin layer 4 may include other heat-fusible resin layers such as a third heat-fusible resin layer and a fourth heat-fusible resin layer on the barrier layer 3 side of the second heat-fusible resin layer 42, in addition to the first heat-fusible resin layer 41 and the second heat-fusible resin layer 42. As the resin constituting the other heat-fusible resin layers, the same resins as described in the first heat-fusible resin layer 41 can be exemplified. In addition, as the thickness of the other heat-fusible resin layers, the same thickness as described in the second heat-fusible resin layer 42 can be exemplified.
[0133] The total thickness of the heat-fusible resin layer 4 is preferably about 100 μm or less, about 85 μm or less, or about 60 μm or less, and may be 5 μm or more, 10 μm or more, 20 μm or more, 30 μm or more, or 40 μm or more. Preferred ranges include about 5 to 100 μm, about 5 to 85 μm, about 5 to 60 μm, about 10 to 100 μm, about 10 to 85 μm, about 10 to 60 μm, about 20 to 100 μm, about 20 to 85 μm, about 20 to 60 μm, about 30 to 100 μm, about 30 to 85 μm, about 30 to 60 μm, about 40 to 100 μm, about 40 to 85 μm, or about 40 to 60 μm.
[0134] [Adhesive layer 5]
[0135] In the external packaging material for a power storage device of the present invention, the adhesive layer 5 is a layer provided between the barrier layer 3 (or the corrosion-resistant film) and the heat-fusible resin layer 4 as necessary in order to firmly bond them together.
[0136] The adhesive layer 5 is formed of a resin that can bond the barrier layer 3 to the thermally fusible resin layer 4. As the resin used to form the adhesive layer 5, for example, the same adhesive as exemplified in the adhesive layer 2 can be used. Among them, as the resin used to form the adhesive layer 5, it is preferred that it contains a polyolefin skeleton, and the polyolefins and acid-modified polyolefins exemplified in the above-mentioned first thermally fusible resin layer 41 can be listed. The resin constituting the adhesive layer 5 contains a polyolefin skeleton, and for example, it can be analyzed by infrared spectroscopy, gas chromatography-mass spectrometry, etc., and the analysis method is not particularly limited. In addition, when analyzing the resin constituting the adhesive layer 5 by infrared spectroscopy, it is preferred to detect the peak from maleic anhydride. For example, when measuring maleic anhydride-modified polyolefin by infrared spectroscopy, at a wave number of 1760cm -1 Nearby and wave number 1780cm -1 A peak derived from maleic anhydride is detected near the 20% peak. However, when the degree of acid modification is low, the peak may become smaller and undetectable. In this case, nuclear magnetic resonance spectroscopy can be used for analysis.
[0137] The adhesive layer 5 may be formed of a cured product of a thermoplastic resin or a thermosetting resin, and is preferably formed of a thermoplastic resin.
[0138] From the viewpoint of firmly bonding the barrier layer 3 and the heat-fusible resin layer 4, the adhesive layer 5 preferably contains an acid-modified polyolefin. As the acid-modified polyolefin, polyolefin modified with carboxylic acid or its anhydride, polypropylene modified with carboxylic acid or its anhydride, maleic anhydride-modified polyolefin, and maleic anhydride-modified polypropylene are particularly preferred.
[0139] In addition, from the viewpoint of reducing the thickness of the storage device packaging material and forming the storage device packaging material with excellent shape stability after molding, the adhesive layer 5 is preferably a cured product of a resin composition containing an acid-modified polyolefin and a curing agent. As the acid-modified polyolefin, the above-mentioned substances are preferably exemplified.
[0140] As described above, in the storage battery device exterior material 10 of the present invention, when the adhesive layer 5 is provided, it is preferred that the first heat-fusible resin layer 41 constituting the surface contains polyolefin and the adhesive layer 5 contains acid-modified polyolefin.
[0141] In addition, the adhesive layer 5 is preferably a cured product of a resin composition containing an acid-modified polyolefin and at least one selected from a compound having an isocyanate group, a compound having an oxazoline group, and a compound having an epoxy group, and is particularly preferably a cured product of a resin composition containing an acid-modified polyolefin and at least one selected from a compound having an isocyanate group and a compound having an epoxy group. In addition, the adhesive layer 5 preferably contains at least one selected from polyurethane, polyester, and epoxy resin, and more preferably contains polyurethane and epoxy resin. As polyester, for example, amide resin is preferred. Amide resin is usually generated by the reaction of a carboxyl group and an oxazoline group. The adhesive layer 5 is more preferably a cured product of a resin composition containing at least one of these resins and the above-mentioned acid-modified polyolefin. Among them, when unreacted products of curing agents such as compounds having an isocyanate group, compounds having an oxazoline group, and epoxy resins remain in the adhesive layer 5, the presence of the unreacted products can be confirmed, for example, by a method selected from infrared spectroscopy, Raman spectroscopy, time-of-flight secondary ion mass spectrometry (TOF-SIMS), etc.
[0142] In addition, from the viewpoint of further improving the adhesion between the barrier layer 3 and the adhesive layer 5, the adhesive layer 5 is preferably a cured product of a resin composition containing a curing agent selected from at least one of an oxygen atom, a heterocycle, a C=N bond, and a C-O-C bond. As a curing agent having a heterocycle, for example, a curing agent having an oxazoline group, a curing agent having an epoxy group, etc. can be cited. In addition, as a curing agent having a C=N bond, a curing agent having an oxazoline group, a curing agent having an isocyanate group, etc. can be cited. In addition, as a curing agent having a C-O-C bond, a curing agent having an oxazoline group, a curing agent having an epoxy group, polyurethane, etc. can be cited. The adhesive layer 5 is a cured product of a resin composition containing these curing agents, for example, which can be confirmed by methods such as gas chromatography-mass spectrometry (GCMS), infrared spectroscopy (IR), time-of-flight secondary ion mass spectrometry (TOF-SIMS), and X-ray photoelectron spectroscopy (XPS).
[0143] As the compound with isocyanate group, there is no particular restriction, from the viewpoint of effectively improving the adhesion of barrier layer 3 and adhesive layer 5, preferably polyfunctional isocyanate compounds are listed. Polyfunctional isocyanate compounds are not particularly limited as long as they are compounds with more than 2 isocyanate groups. As the specific example of polyfunctional isocyanate curing agent, pentane diisocyanate (PDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), materials formed by polymerizing or urate (nurate), their mixtures or copolymers with other polymers, etc. can be listed. In addition, adducts, biuret bodies, isocyanurate bodies, etc. can be listed.
[0144] The content of the compound having an isocyanate group in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This can effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5.
[0145] The compound with oxazoline group is just not particularly limited as long as it is the compound with oxazoline skeleton.As the specific example of the compound with oxazoline group, the compound with polystyrene main chain, the compound with acrylic acid main chain etc. can be enumerated.In addition, as commercially available product, for example, the Epocros series etc. produced by Nippon Catalyst Co., Ltd. can be enumerated.
[0146] The proportion of the compound having an oxazoline group in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This can effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5.
[0147] As a compound having an epoxy group, for example, epoxy resin can be cited. As the epoxy resin, there is no particular limitation as long as it is a resin that can form a cross-linked structure using the epoxy group present in the molecule, and a known epoxy resin can be used. As the weight average molecular weight of the epoxy resin, preferably about 50 to 2000, more preferably about 100 to 1000, and further preferably about 200 to 800. Among them, in the present invention, the weight average molecular weight of the epoxy resin is a value measured by gel permeation chromatography (GPC) under the condition of using polystyrene as a standard.
[0148] Specific examples of epoxy resins include glycidyl ether derivatives of trimethylolpropane, bisphenol A diglycidyl ether, modified bisphenol A diglycidyl ether, novolac glycidyl ether, glycerol polyglycidyl ether, polyglycerol polyglycidyl ether, etc. The epoxy resins may be used alone or in combination of two or more.
[0149] The proportion of the epoxy resin in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5 . This can effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5 .
[0150] The polyurethane is not particularly limited, and known polyurethanes can be used. The adhesive layer 5 may be, for example, a cured product of a two-component curing type polyurethane.
[0151] The proportion of polyurethane in the adhesive layer 5 is preferably in the range of 0.1 to 50% by mass, more preferably in the range of 0.5 to 40% by mass, in the resin composition constituting the adhesive layer 5. This can effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5 in an atmosphere where there are components that cause corrosion of the barrier layer, such as an electrolyte.
[0152] Among them, when the adhesive layer 5 is a cured product of a resin composition containing at least one selected from a compound having an isocyanate group, a compound having an oxazoline group and an epoxy resin, and the above-mentioned acid-modified polyolefin, the acid-modified polyolefin functions as a main agent, and the compound having an isocyanate group, the compound having an oxazoline group and the compound having an epoxy group function as a curing agent, respectively.
[0153] From the viewpoint of effectively suppressing the first heat-fusible resin layer 41 from being destroyed during heat-fusion and improving the sealing property of the external packaging material for a storage device, the total thickness of the adhesive layer 5 and the heat-fusible resin layer 4 is preferably about 50 μm or more, more preferably about 60 μm or more, and further preferably about 70 μm or more, and preferably about 120 μm or less, and more preferably about 100 μm or less. Preferred ranges include about 50 to 120 μm, about 50 to 100 μm, about 60 to 120 μm, about 60 to 100 μm, about 70 to 120 μm, and about 70 to 100 μm.
[0154] In addition, regarding the preferred ratio of the thickness of the first heat-fusible resin layer 41 to the thickness of the second heat-fusible resin layer 42, the thickness of the first heat-fusible resin layer 41 is set to 1.0, and the thickness of the second heat-fusible resin layer 42 is preferably about 1.5 to 6.0, more preferably about 1.7 to 5.5, and further preferably about 2.0 to 5.0. In addition, regarding the preferred ratio of the thickness of the adhesive layer 5, the thickness of the first heat-fusible resin layer 41, and the thickness of the second heat-fusible resin layer 42, the thickness of the first heat-fusible resin layer 41 is set to 1.0, the thickness of the adhesive layer 5 is preferably about 0.5 to 3.0, and the thickness of the second heat-fusible resin layer 42 is about 1.5 to 6.0, more preferably the thickness of the adhesive layer 5 is about 0.7 to 2.3, and the thickness of the second heat-fusible resin layer 42 is about 1.7 to 5.5, and further preferably the thickness of the adhesive layer 5 is about 1.0 to 2.0, and the thickness of the second heat-fusible resin layer 42 is about 2.0 to 5.0.
[0155] In addition, as a specific example of a preferred ratio of the thickness of the first heat-fusible resin layer 41 to the thickness of the second heat-fusible resin layer 42, the thickness of the first heat-fusible resin layer 41 is set to 1.0, and the thickness of the second heat-fusible resin layer 42 can be, for example, 2.0, 2.7, 3.0, 4.0, 5.0, 6.0, etc. In addition, as preferred specific examples of the thickness of the adhesive layer 5, the thickness of the first heat-fusible resin layer 41 and the thickness of the second heat-fusible resin layer 42, the thickness of the first heat-fusible resin layer 41 is set to 1.0, and the following examples can be listed: the thickness of the adhesive layer 5 is 1.0 and the thickness of the second heat-fusible resin layer 42 is 2.0; the thickness of the adhesive layer 5 is 1.7 and the thickness of the second heat-fusible resin layer 42 is 2.7; the thickness of the adhesive layer 5 is 1.3 and the thickness of the second heat-fusible resin layer 42 is 3.0; the thickness of the adhesive layer 5 is 2.0 and the thickness of the second heat-fusible resin layer 42 is 5.0.
[0156] From the viewpoint of effectively suppressing the first heat-fusible resin layer 41 from being destroyed during heat-fusion and improving the sealing property of the external packaging material for a storage device, the thickness of the adhesive layer 5 may be greater than the thickness of the first heat-fusible resin layer 41. For example, when the heat-fusible resin layer 4 is composed of a single layer of the first heat-fusible resin layer 41 and the adhesive layer 5 is provided between the barrier layer 3 and the first heat-fusible resin layer 41, the thickness of the adhesive layer 5 is preferably greater than the thickness of the first heat-fusible resin layer 41. In order to achieve excellent heat-fusion property, the first heat-fusible resin layer 41 is preferably made of a resin that flows more easily at high temperature than the adhesive layer 5. By having such a thickness relationship, the first heat-fusible resin layer 41, which is a part of the heat-fusible resin layer 4 and is composed of a resin that flows more easily, can be made thinner, thereby improving the insulation property of the external packaging material for a storage device. By appropriately adjusting the MFR, melting point, molecular weight, and the like of the resin constituting the first thermally adhesive resin layer 41 , the first thermally adhesive resin layer 41 can be made a resin layer that easily flows at high temperatures.
[0157] In addition, in the external packaging material 10 for a storage device of the present invention, when the heat-fusible resin layer 4 has the first heat-fusible resin layer 41 and the second heat-fusible resin layer 42, it is preferred that the thickness of the second heat-fusible resin layer 42 is greater than the thickness of the adhesive layer 5. The second heat-fusible resin layer 42 has better water barrier properties than the adhesive layer 5 that contributes to adhesion, and thus by having such a thickness relationship, the water barrier properties of the external packaging material for a storage device can be improved.
[0158] From the viewpoint of achieving high insulation after heat fusion, the second heat fusion resin layer 42 is preferably thicker than the adhesive layer 5 , and the adhesive layer 5 is preferably thicker than the first heat fusion resin layer 41 .
[0159] The thickness of the adhesive layer 5 is preferably less than about 60 μm, less than about 50 μm, less than about 40 μm, less than about 30 μm, less than about 20 μm, less than about 10 μm, less than about 8 μm, less than about 5 μm, or less than about 3 μm, and preferably greater than about 0.1 μm, greater than about 0.5 μm, greater than about 5 μm, greater than about 10 μm, or greater than about 20 μm. As the range of the thickness, preferably 0.1 to 60 μm, 0.1 to 50 μm, 0.1 to 40 μm, 0.1 to 30 μm, 0.1 to 20 μm, 0.1 to 10 μm, 0.1 to 8 μm, 0.1 to 5 μm, 0.1 to 3 μm, 0.5 to 60 μm, 0.5 to 50 μm, 0.5 to 40 μm, 0.5 to 30 μm, 0.5 to 20 More specifically, in the case of the adhesive or the cured product of the acid-modified polyolefin and the curing agent exemplified in the adhesive layer 2, preferably about 1 to 10 μm, more preferably 1 μm or more and less than 10 μm, further preferably about 1 to 8 μm, further preferably about 1 to 5 μm, further preferably about 1 to 3 μm. When the resin exemplified as the first heat-fusible resin layer 41 is used, preferably, about 2 to 60 μm, about 2 to 50 μm, about 10 to 60 μm, about 10 to 50 μm, about 20 to 60 μm, about 20 to 50 μm. Among them, when the adhesive layer 5 is an adhesive exemplified as the adhesive layer 2, or a cured product of a resin composition containing an acid-modified polyolefin and a curing agent, the adhesive layer 5 can be formed, for example, by applying the resin composition and curing it by heating. When the resin exemplified as the first heat-fusible resin layer 41 is used, for example, the heat-fusible resin layer 4 and the adhesive layer 5 can be formed by extrusion molding.
[0160] In the external packaging material 10 for a storage battery device of the present invention, specific examples of preferred laminated structures on the side of the barrier layer 3 opposite to the substrate layer 1 side include: a laminated structure in which, starting from the barrier layer 3 side, an adhesive layer 5 having a thickness of about 20 to 60 μm and a first heat-fusible resin layer 41 having a thickness of 20 to 50 μm are laminated in sequence; a laminated structure in which an adhesive layer 5 having a thickness of about 20 to 60 μm and a first heat-fusible resin layer 41 having a thickness of 20 to 40 μm are laminated in sequence; a laminated structure in which an adhesive layer 5 having a thickness of about 5 to 30 μm, a second heat-fusible resin layer 42 having a thickness of about 30 to 80 μm and a first heat-fusible resin layer 41 having a thickness of about 5 to 25 μm are laminated in sequence; a laminated structure in which an adhesive layer 5 having a thickness of about 5 to 20 μm, a second heat-fusible resin layer 42 having a thickness of about 40 to 80 μm and a first heat-fusible resin layer 41 having a thickness of about 5 to 25 μm are laminated in sequence, and the like.
[0161] [Surface coating layer 6]
[0162] In the external packaging material for a storage device of the present invention, for at least one purpose of improving design, electrolyte resistance, scratch resistance, formability, etc., a surface coating layer 6 may be provided on the substrate layer 1 (on the side of the substrate layer 1 opposite to the barrier layer 3) as needed. The surface coating layer 6 is a layer located on the outermost side of the external packaging material for a storage device when the storage device is assembled using the external packaging material for a storage device.
[0163] The surface coating layer 6 is formed of a resin such as polyvinylidene chloride, polyester, polyurethane, acrylic resin, or epoxy resin.
[0164] When the resin forming the surface coating layer 6 is a curable resin, the resin can be any one of a single-liquid curable type and a two-liquid curable type, preferably a two-liquid curable type. As the two-liquid curable resin, for example, two-liquid curable polyurethane, two-liquid curable polyester, two-liquid curable epoxy resin, etc. can be cited. Among these, two-liquid curable polyurethane is preferred.
[0165] As a two-liquid curing polyurethane, for example, a polyurethane containing a main agent containing a polyol compound and a curing agent containing an isocyanate compound can be cited. Preferably, a two-liquid curing polyurethane with a polyol such as polyester polyol, polyether polyol and acrylic polyol as a main agent and an aromatic or aliphatic polyisocyanate as a curing agent is cited. In addition, as a polyol compound, a polyester polyol having a hydroxyl group in the side chain in addition to the hydroxyl group at the end of the repeating unit is preferably used. By forming the surface coating layer 6 from polyurethane, it is possible to impart excellent electrolyte tolerance to the external packaging material for the storage device.
[0166] In the surface coating layer 6, according to the functionality that the surface coating layer 6 or its surface needs to have, at least one of the surface and the inside of the surface coating layer 6 can contain the above-mentioned lubricant or anti-adhesive agent, matting agent, flame retardant, antioxidant, tackifier, antistatic agent and other additives as needed. As additives, for example, microparticles with an average particle size of about 0.5nm to 5μm can be listed. The average particle size of the additive is the median particle size measured using a laser diffraction / scattering particle size distribution measuring device.
[0167] The additive may be any of an inorganic substance and an organic substance. Also, there is no particular limitation on the shape of the additive, and examples thereof include spherical, fibrous, plate-like, amorphous, and flaky shapes.
[0168] As the specific example of additive, talc, silicon dioxide, graphite, kaolin, montmorillonite, mica, hydrotalcite, silica gel, zeolite, aluminum hydroxide, magnesium hydroxide, zinc oxide, magnesium oxide, aluminum oxide, neodymium oxide, antimony oxide, titanium oxide, cerium oxide, calcium sulfate, barium sulfate, calcium carbonate, calcium silicate, lithium carbonate, calcium benzoate, calcium oxalate, magnesium stearate, aluminum oxide, carbon black, carbon nanotube, high melting point nylon, acrylate resin, cross-linked acrylic acid, cross-linked styrene, cross-linked polyethylene, benzoguanamine, gold, aluminum, copper, nickel, etc. can be listed. One additive can be used alone, or two or more can be used in combination. Among these additives, from the viewpoints of dispersion stability and cost, silicon dioxide, barium sulfate, titanium oxide are preferably listed. In addition, the additive can implement various surface treatments such as insulation treatment and high dispersibility treatment on the surface.
[0169] The method for forming the surface coating layer 6 is not particularly limited, and an example thereof includes a method of applying a resin for forming the surface coating layer 6. When an additive is added to the surface coating layer 6, the resin mixed with the additive may be applied.
[0170] The thickness of the surface coating layer 6 is not particularly limited as long as the above-mentioned function as the surface coating layer 6 can be exhibited, and is, for example, about 0.5 to 10 μm, preferably about 1 to 5 μm.
[0171] 3. Method for manufacturing exterior material for power storage device
[0172] The method for manufacturing the external packaging material for a storage device is not particularly limited as long as the layers of the external packaging material for a storage device of the present invention can be stacked to obtain a laminated body, and a method including the steps of stacking at least the base material layer 1, the barrier layer 3 and the heat-fusible resin layer 4 in sequence can be cited. In the method for manufacturing the external packaging material 10 for a storage device of the present invention, the heat-fusible resin layer 4 is composed of a single layer or a plurality of layers, and the first heat-fusible resin layer 41 constituting the surface of the laminated body in the heat-fusible resin layer 4 has a logarithmic attenuation rate ΔE of 0.20 or less at 140°C in a rigid body oscillator measurement. The details of the external packaging material 10 for a storage device of the present invention are as described above.
[0173] As an example of a method for manufacturing an external packaging material for a storage device of the present invention, the following is described. First, a laminated body (hereinafter sometimes referred to as "laminated body A") is formed by laminating a substrate layer 1, an adhesive layer 2, and a barrier layer 3 in sequence. Specifically, the formation of the laminated body A can be performed by the following dry lamination method: an adhesive for forming an adhesive layer 2 is applied on the substrate layer 1 or on the barrier layer 3 whose surface is chemically treated as required by a coating method such as a gravure coating method or a roller coating method, and after drying, the barrier layer 3 or the substrate layer 1 is laminated, and the adhesive layer 2 is cured.
[0174] Next, a heat-fusible resin layer 4 is laminated on the barrier layer 3 of the laminate A. When the heat-fusible resin layer 4 is laminated directly on the barrier layer 3, the heat-fusible resin layer 4 may be laminated on the barrier layer 3 of the laminate A by a method such as a heat lamination method or an extrusion lamination method. In addition, when an adhesive layer 5 is provided between the barrier layer 3 and the heat-fusible resin layer 4, for example, the following methods may be mentioned: (1) a method of laminating the adhesive layer 5 and the heat-fusible resin layer 4 by extruding them on the barrier layer 3 of the laminate A (co-extrusion lamination method, tandem lamination method); (2) a method of separately forming a laminate in which the adhesive layer 5 and the heat-fusible resin layer 4 are laminated, laminating them on the barrier layer 3 of the laminate A by a heat lamination method, or a method of laminating the adhesive layer 5 on the barrier layer 3 of the laminate A to form a laminate, and laminating them together with the heat-fusible resin layer 4 by a heat lamination method. (1) a method for laminating a heat-melting resin layer 4; (2) a method for laminating a heat-melting resin layer 4; (3) a method for laminating a molten adhesive layer 5 between the barrier layer 3 of the laminate A and the heat-melting resin layer 4 previously formed in a sheet form, while using the adhesive layer 5 to adhere the laminate A to the heat-melting resin layer 4 (sandwich lamination method); (4) a method for laminating an adhesive for forming an adhesive layer 5 on the barrier layer 3 of the laminate A by a method of applying a solution and drying it or further baking it, and then laminating a heat-melting resin layer 4 previously formed in a sheet form on the adhesive layer 5.
[0175] When the surface coating layer 6 is provided, the surface coating layer 6 is laminated on the surface of the substrate layer 1 on the opposite side to the barrier layer 3. The surface coating layer 6 can be formed, for example, by coating the above-mentioned resin for forming the surface coating layer 6 on the surface of the substrate layer 1. The order of the process of laminating the barrier layer 3 on the surface of the substrate layer 1 and the process of laminating the surface coating layer 6 on the surface of the substrate layer 1 is not particularly limited. For example, after the surface coating layer 6 is formed on the surface of the substrate layer 1, the barrier layer 3 can be formed on the surface of the substrate layer 1 on the opposite side to the surface coating layer 6.
[0176] By operating as described above, a laminated body is formed by stacking in sequence a surface coating layer 6 arranged as required / a base material layer 1 / an adhesive layer 2 arranged as required / a barrier layer 3 / an adhesive layer 5 arranged as required / a hot-melt adhesive resin layer 4. In order to strengthen the adhesion between the adhesive layer 2 and the adhesive layer 5 arranged as required, further heat treatment may be performed.
[0177] In the external packaging material for a storage device, each layer constituting the laminate can be subjected to surface activation treatment such as corona treatment, sandblasting, acidification, ozone treatment, etc. as needed to improve processing adaptability. For example, by subjecting the surface of the substrate layer 1 opposite to the barrier layer 3 to corona treatment, the printing adaptability of the ink on the surface of the substrate layer 1 can be improved.
[0178] 4. Application of packaging materials for power storage devices
[0179] The outer packaging material for an electric storage device of the present invention is used as a package for sealing and storing electric storage device elements such as a positive electrode, a negative electrode, and an electrolyte. That is, in a package formed by the packaging material for an electric storage device of the present invention, an electric storage device element having at least a positive electrode, a negative electrode, and an electrolyte is stored to form an electric storage device.
[0180] Specifically, by using the external packaging material for an electrical storage device of the present invention, an electrical storage device element having at least a positive electrode, a negative electrode, and an electrolyte is covered in a manner such that the metal terminals connected to the positive electrode and the negative electrode protrude outward, and a flange portion (an area where the heat-fusible resin layers are in contact with each other) is formed at the periphery of the electrical storage device element, and the heat-fusible resin layers of the flange portion are heat-sealed to each other to seal the flange portion, thereby providing an electrical storage device using the external packaging material for an electrical storage device. In the case where the electrical storage device element is housed in a package formed by the external packaging material for an electrical storage device of the present invention, the package is formed in a manner such that the heat-fusible resin portion of the external packaging material for an electrical storage device of the present invention is on the inner side (the surface in contact with the electrical storage device element).
[0181] The external packaging material for the storage device of the present invention can be applied to storage devices such as batteries (including capacitors (condenser), capacitors (capacitor) and the like). In addition, the external packaging material for the storage device of the present invention can be used in both primary batteries and secondary batteries, preferably secondary batteries. There is no particular restriction on the types of secondary batteries to which the external packaging material for the storage device of the present invention can be applied, and examples thereof include lithium ion batteries, lithium ion polymer batteries, all-solid batteries, lead batteries, nickel-hydrogen batteries, nickel-cadmium batteries, nickel-iron batteries, nickel-zinc batteries, silver oxide-zinc batteries, metal-air batteries, multivalent cation batteries, capacitors (condenser), capacitors (capacitor) and the like. Among these secondary batteries, lithium ion batteries and lithium ion polymer batteries can be cited as preferred application objects of the external packaging material for the storage device of the present invention.
[0182] Example
[0183] The present invention will be described in detail below with reference to Examples and Comparative Examples, but the present invention is not limited to the Examples.
[0184] <Manufacturing of exterior materials for power storage devices>
[0185] Example 1 and Comparative Example 1
[0186] As the substrate layer, a polyethylene terephthalate (PET) film (thickness 12 μm) and a stretched nylon (ONy) film (thickness 15 μm) were prepared, and a two-component polyurethane adhesive (polyol compound and aromatic isocyanate compound) (3 μm) was applied on the PET film to bond it to the ONy film. In addition, as a barrier layer, an aluminum foil (JIS H4160: 1994A8021H-O (thickness 40 μm)) was prepared. Next, a two-component polyurethane adhesive (polyol compound and aromatic isocyanate compound) was applied on one surface of the aluminum foil to form an adhesive layer (thickness 3 μm) on the barrier layer. Next, the adhesive layer on the barrier layer was laminated with the substrate layer (ONy film side) by dry lamination, and then an aging treatment was performed to produce a laminate of substrate layer / adhesive layer / barrier layer. Chemical surface treatment was applied to both sides of the aluminum foil. The chemical surface treatment of aluminum foil is carried out as follows: a treatment solution comprising a phenolic resin, a chromium fluoride compound and phosphoric acid is applied by a roller coating method in a chromium coating amount of 10 mg / m 2 (dry mass) was applied on both sides of aluminum foil and baked.
[0187] Next, on the barrier layer of each laminate obtained above, maleic anhydride-modified polypropylene as an adhesive layer (thickness 20 μm), random polypropylene as a second heat-fusible resin layer (thickness 50 μm), and random polypropylene as a first heat-fusible resin layer (thickness 10 μm) were co-extruded, thereby laminating the adhesive layer / second heat-fusible resin layer / first heat-fusible resin layer on the barrier layer to obtain an external packaging material for a storage device in which a base material layer (including an adhesive with a thickness of 30 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (20 μm) / second heat-fusible resin layer (50 μm) / first heat-fusible resin layer (10 μm) was laminated in sequence. The first heat-fusible resin layer of Example 1 and Comparative Example 1 respectively has a logarithmic decrement ΔE at 140° C. as described in Table 1 (values measured using a rigid oscillator model physical property tester).
[0188] Example 2 and Comparative Example 2
[0189] As the substrate layer, a polyethylene terephthalate (PET) film (thickness 12 μm) and a stretched nylon (ONy) film (thickness 15 μm) were prepared, and a two-component polyurethane adhesive (polyol compound and aromatic isocyanate compound) (3 μm) was applied on the PET film to bond it to the ONy film. In addition, as a barrier layer, an aluminum foil (JIS H4160: 1994A8021H-O (thickness 40 μm)) was prepared. Next, a two-component polyurethane adhesive (polyol compound and aromatic isocyanate compound) was applied on one surface of the aluminum foil to form an adhesive layer (thickness 3 μm) on the barrier layer. Next, the adhesive layer on the barrier layer was laminated with the substrate layer (ONy film side) by dry lamination, and then an aging treatment was performed to produce a laminate of substrate layer / adhesive layer / barrier layer. Chemical surface treatment was applied to both sides of the aluminum foil. The chemical surface treatment of aluminum foil is carried out as follows: a treatment solution comprising a phenolic resin, a chromium fluoride compound and phosphoric acid is applied by a roller coating method in a chromium coating amount of 10 mg / m 2 (dry mass) was applied on both sides of aluminum foil and baked.
[0190] Next, on the barrier layer of each laminate obtained above, maleic anhydride-modified polypropylene as an adhesive layer (thickness 40 μm) and random polypropylene as a first heat-fusible resin layer (thickness 40 μm) were coextruded, thereby laminating the adhesive layer / first heat-fusible resin layer on the barrier layer to obtain an external packaging material for a storage device in which a base layer (including an adhesive with a thickness of 30 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (40 μm) / first heat-fusible resin layer (40 μm) were laminated in sequence. The first heat-fusible resin layer of Example 2 and Comparative Example 2 respectively had a logarithmic decrement ΔE at 140°C as described in Table 1 (values measured using a rigid oscillator model physical property tester).
[0191] Example 3
[0192] As the base material layer, instead of using a laminate of polyethylene terephthalate (PET) film (thickness 12 μm) and stretched nylon (ONy) film (thickness 15 μm), a polyethylene terephthalate (PET) film (thickness 25 μm) is used. Otherwise, the same operation as in Example 1 is performed to obtain an external packaging material for a storage device in which a base material layer (thickness 25 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (20 μm) / second thermally fusible resin layer (50 μm) / first thermally fusible resin layer (10 μm) are laminated in sequence.
[0193] Example 4
[0194] As the base material layer, instead of using a laminate of polyethylene terephthalate (PET) film (thickness 12 μm) and stretched nylon (ONy) film (thickness 15 μm), a stretched nylon (ONy) film (thickness 25 μm) is used. Otherwise, the same operation as in Example 1 is performed to obtain an external packaging material for a storage device in which a base material layer (thickness 25 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (20 μm) / second thermally fusible resin layer (50 μm) / first thermally fusible resin layer (10 μm) are stacked in sequence.
[0195] <Measurement of logarithmic decrement ΔE of first thermally fusible resin layer>
[0196] Each of the external packaging materials for storage devices obtained above was cut into a rectangle with a width (TD: Transverse Direction) of 15 mm and a length (MD: Machine Direction) of 45 mm to prepare a test sample (external packaging material 10 for storage devices). Among them, the MD of the external packaging material for storage devices corresponds to the rolling direction (RD) of the aluminum alloy foil, and the TD of the external packaging material for storage devices corresponds to the TD of the aluminum alloy foil. The rolling direction (RD) of the aluminum alloy foil can be distinguished according to the rolling marks. In the case where the MD of the external packaging material for storage devices cannot be determined using the rolling marks of the aluminum alloy foil, it can be determined as follows. As a method for confirming the MD of the external packaging material for storage devices, the cross section of the heat-fusible resin layer of the external packaging material for storage devices is observed using an electron microscope to confirm the island structure, and the direction parallel to the cross section with the largest average diameter of the island in the direction perpendicular to the thickness direction of the heat-fusible resin layer is judged as MD. Specifically, the cross-sections in the length direction of the thermally fusible resin layer and the cross-sections in the direction parallel to the cross-section in the length direction and changing the angle every 10 degrees until the cross-section in the length direction is perpendicular to the cross-section (a total of 10 cross-sections) are observed using electron microscope photographs to confirm the island structure. Next, the shape of each island is observed for each cross-section. For the shape of each island, the straight line distance connecting the leftmost end in the direction perpendicular to the thickness direction of the thermally fusible resin layer and the rightmost end in the perpendicular direction is taken as the diameter y. In each cross-section, the average value of the 20 largest diameters y of the island in order of size is calculated. The direction parallel to the cross-section with the largest average value of the diameter y of the island is judged as MD. A schematic diagram for illustrating the method for measuring the logarithmic attenuation rate ΔE using a rigid body oscillator is shown in Figure 6. A rigid vibrator model physical property tester (model: RPT-3000W, manufactured by A&D Company, Limited) was used, FRB-100 was used for the frame of the vibrator 30, RBP-060 was used for the cylindrical cylinder edge 30a of the edge portion, CHB-100 was used for the hot and cold module 31, and a vibration displacement detector 32 and a hammer 33 were used, and the initial amplitude was set to 0.3 degrees. The measurement surface (first heat-melting resin layer) of the test sample was placed on the hot and cold module 31 with the axis direction of the cylindrical cylinder edge 30a with the vibrator 30 facing upward, and was set on the measurement surface in a manner that the axis direction of the cylindrical cylinder edge 30a with the vibrator 30 was orthogonal to the MD direction of the test sample. In addition, in order to prevent the test sample from floating or warping during the measurement, a tape was attached to the part of the test sample that did not affect the measurement result and fixed to the hot and cold module 31. The cylindrical cylinder edge 30a was brought into contact with the surface of the first heat-melting resin layer. Next, the logarithmic decrement ΔE of the first heat-melting resin layer was measured at a temperature increase rate of 3°C / min in the temperature range of 30°C to 200°C using the hot and cold module 31. The logarithmic decrement ΔE of the first heat-melting resin layer of the test sample (exterior packaging material 10 for storage device) was measured when the surface temperature reached 140°C. (The test sample that had been measured once was not used, and a newly cut sample was used, and the average value of the three measurements (N=3) was used.) For the first heat-melting resin layer, each exterior packaging material for storage device obtained above was immersed in 15% hydrochloric acid to dissolve the base material layer and the aluminum foil, and the test sample that only became the adhesive layer and the heat-melting resin layer was fully dried, and the logarithmic decrement ΔE was measured. The logarithmic decrements ΔE at 140°C are shown in Table 1. The logarithmic decrement ΔE is calculated by the following formula.
[0197] ΔE=[ln(A1 / A2)+ln(A2 / A3)+...+ln(An / An+1)] / n
[0198] A: Amplitude
[0199] n: wave number
[0200] The logarithmic decrement ΔE at 80°C was measured in the same manner as in <Measurement of logarithmic decrement ΔE of first heat-fusible resin layer> except that the logarithmic decrement ΔE at the surface temperature of the first heat-fusible resin layer reached 80°C. The results are shown in Table 1.
[0201] <Measurement of Remaining Ratio of Thickness of First Thermally Fusible Resin Layer>
[0202] The above-obtained external packaging material for storage devices was cut into pieces of 150 mm in length and 60 mm in width to prepare a test sample (external packaging material 10 for storage devices). Next, the first heat-fusible resin layers of the test sample made of the same external packaging material for storage devices were made to face each other. Next, in this state, a metal plate with a width of 7 mm was used to heat and pressurize the first heat-fusible resin layers from both sides of the test sample in the stacking direction at a temperature of 190°C, the surface pressure recorded in Table 1, and a time of 3 seconds, so that the first heat-fusible resin layers were heat-fused. Next, a slicer was used to cut the heat-fused portion of the test sample in the stacking direction, and the thickness of the two first heat-fusible resin layers heat-fused to each other was measured for the exposed cross section. The same operation was performed on the test sample before heat fusion, and the slicer was used to cut it in the stacking direction, and the thickness of the two first heat-fusible resin layers was measured for the exposed cross section. The ratio of the total thickness of the two first heat-fusible resin layers after heat fusion to the total thickness of the two first heat-fusible resin layers before heat fusion was calculated, and the remaining ratio (%) of the total thickness of the two first heat-fusible resin layers was measured.
[0203] <Observation of the cross-sectional structure of the heat-welded portion>
[0204] Heat and pressure were applied to each external packaging material for the storage device under the conditions of a width of 7 mm, a temperature of 190°C, a pressure of 0.5 MPa, and 3 seconds to thermally fuse the heat-fusible resin layers to each other, thereby forming the above-mentioned heat-fused portion. Next, the heat-fused portion was cut in the thickness direction using a slicer, and the obtained cross section was observed using a microscope. The microscope used was VK-9710 manufactured by KEYENCE CORPORATION. For reference, microscopic photographs of the cross sections of Examples 1 and 2 and Comparative Examples 1 and 2 are shown in FIG. Figure 7 (Example 1), Figure 8 (Example 2), Fig. 9 (Comparative Example 1) and Fig.10 (Comparative Example 2). Figures 7-10 The micrograph of shows the positions of the base material layer 1, the adhesive layer 2, the barrier layer 3, the adhesive layer 5, the first thermally-adhesive resin layer 41, and the second thermally-adhesive resin layer 42, respectively.
[0205] Based on the microscope photographs, the cross-sectional structure of the heat-welded portion was evaluated according to the following criteria. The results are shown in Table 1. Among them, the following evaluations A and B were evaluated as being able to effectively suppress the first heat-weldable resin layer from being destroyed during heat-welding.
[0206] A: In the heat-welded portion, the heat-weldable resin layer does not protrude inward (toward the space where the external packaging material for the power storage device is housed)
[0207] B: In the heat-welded portion, the heat-weldable resin layer slightly protrudes inward (toward the space where the external packaging material for the power storage device is housed)
[0208] C: At the heat-welded portion, the heat-weldable resin layer greatly protrudes inward (toward the space where the external packaging material for the power storage device is housed) [Table 1]
[0209]
[0210] In Tables 1 and 2, DL represents an adhesive for bonding a polyethylene terephthalate film to a stretched nylon film. In the second heat-fusible resin layer / first heat-fusible resin layer, the expression "-" means that the second heat-fusible resin layer is not provided.
[0211] The results shown in Table 1 show that in the storage battery device exterior materials of Examples 1-4, the logarithmic decrement ΔE of the first heat-fusible resin layer constituting the surface at 140° C. is 0.20 or less, and the first heat-fusible resin layer can be effectively prevented from being destroyed during heat fusion.
[0212] As described above, the present invention provides the following aspects of the invention.
[0213] Item 1. An external packaging material for a storage device, comprising a laminate having at least a substrate layer, a barrier layer and a heat-fusible resin layer in sequence, wherein the heat-fusible resin layer is composed of a single layer or a plurality of layers, and among the heat-fusible resin layers, the first heat-fusible resin layer constituting the surface of the laminate has a logarithmic attenuation rate ΔE of less than 0.20 at 140°C in a rigid body oscillator measurement.
[0214] Item 2. The external packaging material for a power storage device according to Item 1, wherein the thickness of the first thermally fusible resin layer is 5 μm or more and 25 μm or less.
[0215] Item 3. An exterior material for a storage device as described in Item 1 or 2, wherein the first heat-fusible resin layers of the stacked body are placed opposite to each other, and after heating and pressurizing in the stacking direction at a temperature of 190°C, a surface pressure of 2.0 MPa, and a time of 3 seconds, the residual ratio of the total thickness of the two relative first heat-fusible resin layers is greater than 30%.
[0216] Item 4. The external packaging material for a power storage device according to any one of Items 1 to 3, wherein the resin constituting the first thermally fusible resin layer contains a polyolefin skeleton.
[0217] Item 5. The external packaging material for a power storage device according to any one of Items 1 to 4, further comprising an adhesive layer between the barrier layer and the thermally adhesive resin layer.
[0218] Item 6. The external packaging material for a power storage device according to Item 5, wherein the total thickness of the adhesive layer and the thermally fusible resin layer is 50 μm or more.
[0219] Item 7. The external packaging material for a power storage device according to Item 5 or 6, wherein the thickness of the adhesive layer is greater than or equal to the thickness of the first thermally fusible resin layer.
[0220] Item 8. An exterior material for a storage device as described in any one of Items 5 to 7, wherein the heat-fusible resin layer comprises the first heat-fusible resin layer and the second heat-fusible resin layer in sequence from the surface side of the laminate, and the thickness of the second heat-fusible resin layer is greater than the thickness of the adhesive layer.
[0221] Item 9. The power storage device exterior material according to any one of Items 5 to 8, wherein a thickness of the second heat-fusible resin layer is greater than a thickness of the first heat-fusible resin layer.
[0222] Item 10. The external packaging material for a power storage device according to any one of Items 5 to 9, wherein the adhesive layer has a thickness of 50 μm or less.
[0223] Item 11. The power storage device exterior material according to any one of Items 1 to 10, wherein a lubricant is present on a surface of the first thermally adhesive resin layer.
[0224] Item 12. A method for manufacturing an exterior material for a storage device, comprising the step of stacking at least a substrate layer, a barrier layer and a heat-fusible resin layer in sequence to obtain a laminate, wherein the heat-fusible resin layer is composed of a single layer or a plurality of layers, and among the heat-fusible resin layers, the first heat-fusible resin layer constituting the surface of the laminate has a logarithmic attenuation rate ΔE of less than 0.20 at 140°C in a rigid body oscillator measurement.
[0225] Item 13. An electricity storage device, comprising an electricity storage device element having at least a positive electrode, a negative electrode, and an electrolyte housed in a package formed of the electricity storage device exterior material according to any one of Items 1 to 11.
[0226] Explanation of symbols
[0227] 1: base material layer; 2: adhesive layer; 3: barrier layer; 4: heat-fusible resin layer; 5: adhesive layer; 6: surface coating layer; 10: exterior material for power storage device; 41: first heat-fusible resin layer; 42: second heat-fusible resin layer.
Claims
1. An external packaging material for an electric storage device, characterized in that: The invention is composed of a laminated body having at least a base material layer, a barrier layer and a heat-fusible resin layer in this order, The heat-fusible resin layer is composed of a single layer or multiple layers. Among the thermally fusible resin layers, a first thermally fusible resin layer constituting the surface of the laminate has a logarithmic decrement ΔE of 0.20 or less at 140° C. in a rigid body oscillator measurement.
2. The exterior material for an electric storage device according to claim 1, wherein: The thickness of the first thermally fusible resin layer is 5 μm or more and 25 μm or less.
3. The exterior material for an electric storage device according to claim 1 or 2, wherein: The first heat-fusible resin layers of the laminate are placed opposite to each other and heated and pressed in the lamination direction at a temperature of 190°C, a surface pressure of 2.0 MPa, and a time of 3 seconds, and the residual ratio of the total thickness of the two opposing first heat-fusible resin layers is greater than 30%.
4. The external packaging material for an electric storage device according to any one of claims 1 to 3, wherein The resin constituting the first thermally fusible resin layer includes a polyolefin skeleton.
5. The external packaging material for an electric storage device according to any one of claims 1 to 4, wherein An adhesive layer is provided between the barrier layer and the thermally adhesive resin layer.
6. The exterior material for an electric storage device according to claim 5, wherein: The total thickness of the adhesive layer and the thermally adhesive resin layer is 50 μm or more.
7. The exterior material for an electric storage device according to claim 5 or 6, wherein: The thickness of the adhesive layer is greater than or equal to the thickness of the first thermally-adhesive resin layer.
8. The external packaging material for an electric storage device according to any one of claims 5 to 7, wherein The heat-fusible resin layer includes the first heat-fusible resin layer and the second heat-fusible resin layer in this order from the surface side of the laminate. The thickness of the second thermally-adhesive resin layer is greater than the thickness of the adhesive layer.
9. The external packaging material for an electric storage device according to any one of claims 5 to 8, wherein The second thermally adhesive resin layer has a thickness greater than that of the first thermally adhesive resin layer.
10. The external packaging material for an electric storage device according to any one of claims 5 to 9, wherein The thickness of the adhesive layer is 50 μm or less.
11. The external packaging material for an electric storage device according to any one of claims 1 to 10, wherein A lubricant is present on the surface of the first thermally-adhesive resin layer.
12. A method for manufacturing an external packaging material for an electric storage device, characterized in that: The method comprises the steps of laminating at least a base material layer, a barrier layer and a heat-fusible resin layer in sequence to obtain a laminate. The heat-fusible resin layer is composed of a single layer or multiple layers. Among the thermally fusible resin layers, a first thermally fusible resin layer constituting the surface of the laminate has a logarithmic decrement ΔE of 0.20 or less at 140° C. in a rigid body oscillator measurement.
13. An electric storage device, characterized in that: An electricity storage device element including at least a positive electrode, a negative electrode, and an electrolyte is housed in a package formed of the electricity storage device exterior material according to any one of claims 1 to 11.
